Two-component polyurethane adhesive composition
By developing a two-component polyurethane glue with high thermal conductivity and adding appropriate fillers, the problem of difficulty in achieving high thermal conductivity, mechanical stability and low wear in the prior art is solved, and an efficient and economical bonding layer suitable for thermal management of electric vehicle batteries is achieved.
Patent Information
- Application Number
- JP2024559457
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-04-06
- Filing Date
- 2023-04-05
- Publication Date
- 2025-04-16
AI Technical Summary
The prior art is difficult to achieve high thermal conductivity, good mechanical stability, low wear and suitable extension at the same time, providing efficient and economical solutions for the thermal management and manufacturing of electric vehicle batteries.
A two-component polyurethane glue with high thermal conductivity was developed, using NCO-terminated prepolymer and OH-terminal prepolymer as the base components, and a variety of fillers such as aluminum trihydride and graphite were added to form a bonding layer with high thermal conductivity, strong adhesion and low wear through reaction and mixing.
It realizes high thermal conductivity, strong adhesion and low wear adhesive layer, suitable for thermal management of electric vehicle batteries, reduces manufacturing costs and improves product performance.
Smart Images

Figure 2025511886000001 
Figure 2025511886000002 
Figure 2025511886000003
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to U.S. Provisional Application No. 63 / 327,867, filed April 6, 2022, which is incorporated herein by reference.
[0002] The present invention relates to the field of two-part polyurethane adhesive compositions. [Background technology]
[0003] The demand for affordable electric vehicles with longer autonomous driving range is rapidly accelerating innovation in electric vehicle (EV) battery concepts. Higher energy density, lighter weight, more durable and more economical EV battery concepts have been developed over the past decade.
[0004] Innovation efforts are mainly focused in two directions: 1. To extend the autonomous driving range by increasing the energy packing density, and 2. To reduce the price of the battery. Several strategies exist on the market to achieve higher energy density of the cells in order to reduce the weight and extend the autonomous driving range of the battery, all of which include thermal management concepts to optimize the operating conditions and life of the battery. A typical cell generates heat under standard operating conditions and during charging. The optimal operating temperature of the cell is between 25 and 40 °C. The heat generated by the cell during operation is dissipated to a cooling plate. The cells or modules are connected to the cooling plate through a thermally conductive material. Thermally conductive adhesives are needed to increase the mechanical stability of the battery.
[0005] One way to reduce the cost of a battery is to reduce its manufacturing cost, for example, the manufacturing process. To reduce the cost of adhesive, one way is to reduce or eliminate the process of surface preparation for adhesion. Another way to reduce the cost of a battery is to shorten the duration of the manufacturing process.
[0006] The ideal requirements for a thermally conductive adhesive for batteries are: Thermal conductivity of 1W / mK or higher Elongation at break of over 25% enabling joining of materials with different thermal expansion coefficients Flame retardant -Low wear to reduce maintenance of dispensing equipment 10 10 Volume resistivity of Ωm or more Good adhesion to multiple materials used in battery assemblies, including bare aluminum, laser pre-treated steel, and nickel-plated steel
[0007] Some or all of these properties are difficult to achieve. There remains a need for new and improved thermally conductive adhesives. Summary of the Invention [Means for solving the problem]
[0008] In a first aspect, the present invention provides a two-part thermally conductive polyurethane adhesive comprising: A. a first component (isocyanate) comprising an NCO-terminated prepolymer made by reacting at least one polyol with at least one polyisocyanate; B. A second component (polyol) comprising an OH-terminated prepolymer made by reacting at least one polyol with at least one polyisocyanate and a catalyst capable of catalyzing the reaction of isocyanate groups with OH groups; Component A and / or Component B may comprise the following fillers: Aluminum trihydroxide having a multimodal particle size distribution; Graphite having a spherical particle shape, and Graphite having an aspect ratio of greater than 2; As a result, a two-part thermally conductive polyurethane adhesive is provided in which, when Components A and B are mixed together to form the adhesive mixture, the adhesive mixture comprises greater than 40% by weight aluminum trihydroxide and greater than 8% by weight graphite.
[0009] In a second aspect, the present invention provides a kit for making an adhesive mixture, comprising: A. a first component (isocyanate) comprising an NCO-terminated prepolymer made by reacting at least one polyol with at least one polyisocyanate; B. A second component (polyol) comprising an OH-terminated prepolymer made by reacting at least one polyol with at least one polyisocyanate and a catalyst capable of catalyzing the reaction of isocyanate groups with OH groups; Component A and / or Component B may comprise the following fillers: Aluminum trihydroxide having a multimodal particle size distribution; Graphite having a spherical particle shape, and Graphite having an aspect ratio of greater than 2; As a result, a kit is provided in which, when component A and component B are mixed together to form an adhesive mixture, the adhesive mixture comprises greater than 40% by weight aluminum trihydroxide and greater than 8% by weight graphite.
[0010] In a third aspect, the present invention provides a method for bonding two or more substrates, comprising the steps of: (1) A two-component thermally conductive polyurethane adhesive, A. a first component (isocyanate) comprising an NCO-terminated prepolymer made by reacting at least one polyol with at least one polyisocyanate; B. A second component (polyol) comprising an OH-terminated prepolymer made by reacting at least one polyol with at least one polyisocyanate and a catalyst capable of catalyzing the reaction of isocyanate groups with OH groups; Component A and / or Component B may comprise the following fillers: Aluminum trihydroxide having a multimodal particle size distribution; Graphite having a spherical particle shape, and Graphite having an aspect ratio of greater than 2; As a result, a two-part thermally conductive polyurethane adhesive is provided, whereby when component A and component B are mixed together to form the adhesive mixture, the adhesive mixture comprises greater than 40% by weight aluminum trihydroxide and greater than 8% by weight graphite; (2) mixing the first component and the second component to obtain an adhesive mixture; (3) applying the adhesive mixture to a first substrate; (4) placing the first substrate in adhesive contact with a second substrate; (5) curing the adhesive mixture.
[0011] In a fourth aspect, the present invention provides an adhesive assembly comprising: (1) a first substrate; (2) a second substrate; The first substrate and the second substrate are A. a first component (isocyanate) comprising an NCO-terminated prepolymer made by reacting at least one polyol with at least one polyisocyanate; B. are bonded together using a cured adhesive produced by mixing and curing a second component (polyol) that contains an OH-terminated prepolymer made by reacting at least one polyol with at least one polyisocyanate and a catalyst capable of catalyzing the reaction of isocyanate groups with OH groups; Component A and / or Component B may comprise the following fillers: Aluminum trihydroxide having a multimodal particle size distribution; Graphite having a spherical particle shape, and Graphite having an aspect ratio of greater than 2; As a result, when Components A and B are mixed together to form an adhesive mixture, the adhesive mixture provides an adhesive assembly comprising greater than 40% by weight aluminum trihydroxide and greater than 8% by weight graphite. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The inventors have found that using the two-part polyurethane adhesives of the present invention it is possible to achieve good thermal conductivity, high bond strength to multiple substrates, low abrasion, flame retardancy and sufficient elongation.
[0013] Definitions and Abbreviations MDI 4,4'-methylenebis(phenylisocyanate) HDI Hexamethylene Diisocyanate IPDI Isophorone Diisocyanate PU Polyurethane GPC Gel Permeation Chromatography RH Relative Humidity ATH Aluminum trihydroxide
[0014] The equivalent weight and molecular weight were determined by gel permeation chromatography (GPC) using a Malvern Viscothek GPC max instrument. Tetrahydrofuran (THF) was used as the eluent, PL GEL MIXED D (Agilent, 300*7.5mm, 5μm) was used as the column, and MALVERN Viscotek TDA (integrated refractive index viscometer and light scattering) was used as the detector.
[0015] The particle size of ATH was measured using laser diffraction using water containing 0.01 wt % sodium pyrophosphate as the suspension medium.
[0016] The particle size and aspect ratio of the graphite were determined according to DIN 66165 part 1 using sieves of 63-5000 μm (according to DIN 4188).
[0017] Component A (Isocyanate) Component A comprises an NCO-terminated prepolymer made by reacting at least one polyol with at least one polyisocyanate.
[0018] The at least one polyol used to make the NCO-terminated prepolymer is preferably a polyether polyol.
[0019] The at least one polyol used to prepare the NCO-terminated prepolymer is preferably selected from polyols having a functionality of 2 or more, more preferably from 2 to 3, such as diols, triols and mixtures thereof. Diols are particularly preferred.
[0020] Preferred polyether polyols used to make the NCO-terminated prepolymers include poly(C2-C4-alkylene oxide) polyols, particularly poly(ethylene oxide) polyols, poly(propylene oxide) polyols, poly(tetramethylene oxide) polyols, and mixtures thereof, with poly(propylene oxide) polyols being especially preferred.
[0021] In a preferred embodiment, the polyol used to prepare the NCO-terminated prepolymer is selected from poly(C2-C4-alkylene oxide) polyols, in particular poly(ethylene oxide) polyols having a functionality of 2-3, poly(propylene oxide) polyols having a functionality of 2-3, poly(tetramethylene oxide) polyols having a functionality of 2-3, and mixtures thereof, with poly(propylene oxide) polyols having a functionality of 2-3 being particularly preferred.
[0022] The at least one polyol used to prepare the NCO-terminated prepolymer preferably has a molecular weight of 400 to 2,500 Da.
[0023] The at least one polyol used to make the NCO-terminated prepolymer preferably has an average equivalent weight of from 200 to 1,250 g / eq, more preferably from 210 to 520 g / eq.
[0024] In a preferred embodiment, the at least one polyol used to prepare the NCO-terminated prepolymer is a mixture of polyols, in particular a mixture comprising a polyol having an average equivalent weight of 200-250 g / eq and a polyol having an average equivalent weight of 475-550 g / eq. In a particularly preferred embodiment, the at least one polyol used to prepare the NCO-terminated prepolymer is a mixture of a polyol having an equivalent weight of 200-220 g / eq and a polyol having an equivalent weight of 500-520 g / eq.
[0025] In a particularly preferred embodiment, the at least one polyol used to prepare the NCO-terminated prepolymer is a mixture of a poly(propylene oxide)-based polyol having an average equivalent weight of 200-250 g / eq and a poly(propylene oxide)-based polyol having an average equivalent weight of 475-550 g / eq. In a particularly preferred embodiment, the at least one polyol used to prepare the NCO-terminated prepolymer is a mixture of a poly(propylene oxide)-based polyol having an equivalent weight of 200-220 g / eq and a poly(propylene oxide)-based polyol having an equivalent weight of 500-520 g / eq.
[0026] In a particularly preferred embodiment, the at least one polyol used to prepare the NCO-terminated prepolymer is a mixture of a poly(propylene oxide)-based diol having an average equivalent weight of 200-250 g / eq and a poly(propylene oxide)-based diol having an average equivalent weight of 475-550 g / eq. In a particularly preferred embodiment, the at least one polyol used to prepare the NCO-terminated prepolymer is a mixture of a poly(propylene oxide)-based diol having an equivalent weight of 200-220 g / eq and a poly(propylene oxide)-based diol having an equivalent weight of 500-520 g / eq.
[0027] In a particularly preferred embodiment, the at least one polyol used to prepare the NCO-terminated prepolymer comprises a poly(propylene oxide)-based polyol (P1) having an average equivalent weight of 200-250 g / eq and a poly(propylene oxide)-based polyol (P2) having an average equivalent weight of 475-550 g / eq, with a ratio of P1:P2 of 0.35-0.55, more preferably 0.43-0.47. In a particularly preferred embodiment, the at least one polyol used to prepare the NCO-terminated prepolymer is a mixture of a poly(propylene oxide)-based polyol (P1) having an equivalent weight of 200-220 g / eq and a poly(propylene oxide)-based polyol (P2) having an equivalent weight of 500-520 g / eq, with a ratio of P1:P2 of 0.35-0.55, more preferably 0.43-0.47.
[0028] In a particularly preferred embodiment, at least one polyol used to prepare the NCO-terminated prepolymer is a mixture of a poly(propylene oxide)-based diol (P1) having an average equivalent weight of 200-250 g / eq and a poly(propylene oxide)-based diol (P2) having an average equivalent weight of 475-550 g / eq, with a ratio of P1:P2 of 0.35-0.55, more preferably 0.43-0.47. In a particularly preferred embodiment, at least one polyol used to prepare the NCO-terminated prepolymer is a mixture of a poly(propylene oxide)-based diol (P1) having an equivalent weight of 200-220 g / eq and a poly(propylene oxide)-based diol (P2) having an equivalent weight of 500-520 g / eq, with a ratio of P1:P2 of 0.35-0.55, more preferably 0.43-0.47.
[0029] In a preferred embodiment, the total polyol content in the NCO-terminated prepolymer is from 9 to 20% by weight, more preferably from 10 to 15% by weight, and particularly preferably from 12 to 14% by weight, based on the total weight of component A.
[0030] In another preferred embodiment, component A comprises a poly(propylene oxide) diol having an equivalent weight of 200 to 250 g / eq and a poly(propylene oxide)-based diol having an average equivalent weight of 475 to 550 g / eq.
[0031] In another preferred embodiment, component A comprises 2 to 10% by weight, more preferably 3 to 6% by weight, more particularly preferably 4 to 5% by weight of poly(propylene oxide) diol having an equivalent weight of 200 to 250 g / eq.
[0032] In another preferred embodiment, component A comprises 6 to 15 wt. %, more preferably 8 to 12 wt. %, particularly preferably 9 to 10 wt. % of a poly(propylene oxide)-based diol having an average equivalent weight of 475 to 550 g / eq.
[0033] In a particularly preferred embodiment, component A comprises 2 to 10 wt. %, more preferably 3 to 6 wt. %, more particularly preferably 4 to 5 wt. %, of a poly(propylene oxide) diol having an equivalent weight of 200 to 250 g / eq, and component A comprises 6 to 15 wt. %, more preferably 8 to 12 wt. %, particularly preferably 9 to 10 wt. %, of a poly(propylene oxide)-based diol having an average equivalent weight of 475 to 550 g / eq.
[0034] In another particularly preferred embodiment, component A comprises 2 to 10% by weight, more preferably 3 to 6% by weight, more particularly preferably 4 to 5% by weight of a poly(propylene oxide) diol (P1) having an equivalent weight of 200 to 250 g / eq and component A comprises 6 to 15% by weight, more preferably 8 to 12% by weight, particularly preferably 9 to 10% by weight of a poly(propylene oxide)-based diol (P2) having an average equivalent weight of 475 to 550 g / eq, the ratio P1:P2 being 0.35 to 0.55, more preferably 0.43 to 0.47.
[0035] The at least one polyisocyanate used to prepare the NCO-terminated prepolymer may be aliphatic or aromatic, with aromatic being preferred. Examples of suitable diisocyanates include toluene diisocyanate (TDI), hexamethylene diisocyanate (HDI), naphthalene diisocyanate (NDI), methylene biscyclohexyl isocyanate (HMDI) (hydrogenated MDI), MDI (especially 4,4'- and 4,2-MDI) and isophorone diisocyanate (IPDI), with MDI being particularly preferred.
[0036] In a preferred embodiment, the polyisocyanate used to prepare the NCO-terminated prepolymer is MDI with a functionality of 2 or more, in particular with a functionality of 2 to 3. Particularly preferably, mixtures of MDIs are used, in particular mixtures of MDIs with a functionality of 2 to 2.3 and MDIs with a functionality of 2.5 to 3, in particular mixtures of MDIs with a functionality of 2.2 and MDIs with a functionality of 2.7.
[0037] The total polyisocyanate content of Component A is preferably from 20 to 40% by weight, more preferably from 25 to 35% by weight, and particularly preferably from 28 to 32% by weight, based on the total weight of Component A.
[0038] In a preferred embodiment, component A comprises 25 to 35% by weight, more preferably 28 to 32% by weight, particularly preferably 30 to 31% by weight, of MDI having a functionality of 2 to 2.3, particularly preferably 2.2, based on the total weight of component A.
[0039] In another preferred embodiment, component A comprises 0.25 to 1% by weight, more preferably 0.3 to 0.8% by weight, particularly preferably 0.5 to 0.7% by weight, of MDI having a functionality of 2.5 to 3, particularly preferably 2.7, based on the total weight of component A.
[0040] In a particularly preferred embodiment, component A comprises 25 to 35% by weight, more preferably 28 to 32% by weight, particularly preferably 30 to 31% by weight, of MDI having a functionality of 2 to 2.3, particularly preferably 2.2, based on the total weight of component A, and 0.25 to 1% by weight, more preferably 0.3 to 0.8% by weight, particularly preferably 0.5 to 0.7% by weight, of MDI having a functionality of 2.5 to 3, particularly preferably 2.7, based on the total weight of component A.
[0041] The polyisocyanate is preferably used at a 4:1 NCO equivalent to the OH groups in the polyol to ensure that the prepolymer is NCO terminated.
[0042] Some examples of preferred NCO-terminated prepolymer components are as follows: 1. Polyols: based on the total weight of component A, 2 to 10% by weight, more preferably 3 to 6% by weight, more particularly preferably 4 to 5% by weight of poly(propylene oxide) diols having an equivalent weight of 200 to 250 g / eq, and 6 to 15% by weight, more preferably 8 to 12% by weight, particularly preferably 9 to 10% by weight of poly(propylene oxide)-based diols having an average equivalent weight of 475 to 550 g / eq, and Isocyanates: 25 to 35% by weight, more preferably 28 to 32% by weight, particularly preferably 30 to 31% by weight, based on the total weight of component A, of MDI having a functionality of 2 to 2.3, particularly preferably 2.2, and 0.25 to 1% by weight, more preferably 0.3 to 0.8% by weight, particularly preferably 0.5 to 0.7% by weight, based on the total weight of component A, of MDI having a functionality of 2.5 to 3, particularly preferably 2.7. 2. Polyol: 4-5% by weight of poly(propylene oxide) diol having an equivalent weight of 200-250 g / eq, and 9-10% by weight of poly(propylene oxide)-based diol having an average equivalent weight of 475-550 g / eq, and Isocyanates: 30 to 31% by weight, based on the total weight of component A, of MDI having a functionality of 2 to 2.3, particularly preferably 2.2, and 0.5 to 0.7% by weight, based on the total weight of component A, of MDI having a functionality of 2.5 to 3, particularly preferably 2.7.
[0043] Component A may further comprise an adhesion promoter, which is preferably a reactive silane.
[0044] The reactive silane is any silane that contains a mercapto group, a primary or secondary amine group, or a hydrolyzable silylalkoxy group covalently bonded to an epoxy group.
[0045] In a particularly preferred embodiment, the reactive silane is an epoxy silane.Preferably, the epoxy silane is selected from glycidyloxyalkyl(trialkoxy)silane and glycidyloxyalkyl(methyl-dialkoxy)silane.Examples of suitable epoxy silanes include tris(diethylene glycol methyl ether)silyl propylene glycidyl ether, (3-glycidyloxypropyl)trimethoxysilane, (3-glycidyloxypropyl)triethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 2-(3,4-epoxycyclohexyl)-ethyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)-ethyltriethoxysilane, with (3-glycidyloxypropyl)trimethoxysilane being particularly preferred.
[0046] If used, the reactive silane is preferably present in Component A at 0.1 to 1 wt. %, more preferably 0.25 to 0.75 wt. %, and especially preferably 0.4 to 0.6 wt. %, based on the total weight of Component A.
[0047] In a preferred embodiment, component A contains 0.1 to 1 wt %, more preferably 0.25 to 0.75 wt %, and particularly preferably 0.4 to 0.6 wt % of glycidyloxypropyl)trimethoxysilane, based on the total weight of component A.
[0048] The NCO-terminated prepolymer of Component A is made by mixing at least one polyol with at least one polyisocyanate, preferably under vacuum, at a temperature ranging from 60 to 80°C, more preferably 70 to 75°C.
[0049] If used, the remaining ingredients of Component A, such as fillers and adhesion promoters, are added to the prepolymer and mixed until uniform, then Component A is stored in a moisture-proof container.
[0050] Component B (Polyol) Component B comprises an OH-terminated prepolymer made by reacting at least one polyol with at least one polyisocyanate.
[0051] The at least one polyol used to prepare the OH-terminated prepolymer is preferably a polyether polyol.
[0052] The at least one polyol used to prepare the OH-terminated prepolymer is preferably selected from polyols having a functionality of 2 or more, more preferably 3 or more.
[0053] Preferred polyether polyols used to make the OH-terminated prepolymers include poly(C2-C4-alkylene oxide) polyols, particularly poly(ethylene oxide) polyols, poly(propylene oxide) polyols, poly(tetramethylene oxide) polyols, and mixtures thereof, with poly(propylene oxide) polyols being especially preferred.
[0054] In a preferred embodiment, the polyol used to prepare the OH-terminated prepolymer is selected from poly(C2-C4-alkylene oxide) polyols, in particular poly(ethylene oxide) polyols with a functionality of 3 or greater, poly(propylene oxide) polyols with a functionality of 3 or greater, poly(tetramethylene oxide) polyols with a functionality of 3 or greater, and mixtures thereof, with poly(propylene oxide) polyols with a functionality of 3 or greater being particularly preferred.
[0055] The at least one polyol used to prepare the OH-terminated prepolymer preferably has an average equivalent weight of 800 to 1,800 g / eq, more preferably 1,200 to 1,700 g / eq.
[0056] In a preferred embodiment, the at least one polyol used to make the OH-terminated prepolymer is a triol having an average equivalent weight of 800 to 1,800 g / eq, more preferably 1,200 to 1,700 g / eq.
[0057] In another preferred embodiment, the at least one polyol used to make the OH-terminated prepolymer is a poly(propylene oxide)-based triol having an average equivalent weight of 800 to 1,800 g / eq, more preferably 1,200 to 1,700 g / eq.
[0058] In a particularly preferred embodiment, at least one polyol used to make the OH-terminated prepolymer is a poly(propylene oxide)-based triol having an average equivalent weight of 1,500 to 1,700 g / eq.
[0059] The at least one polyol is preferably used in an amount of 25 to 40% by weight, more preferably 27 to 35% by weight, particularly preferably 32 to 34% by weight, based on the total weight of component B.
[0060] In a preferred embodiment, Component B comprises 25 to 40 wt. %, more preferably 27 to 35 wt. %, and particularly preferably 32 to 34 wt. %, of a poly(propylene oxide)-based triol having an average equivalent weight of 1,500 to 1,700 g / eq, based on the total weight of Component B.
[0061] The at least one polyisocyanate used to prepare the OH-terminated prepolymer may be aliphatic or aromatic, preferably aromatic. Examples of suitable diisocyanates include toluene diisocyanate (TDI), hexamethylene diisocyanate (HDI), naphthalene diisocyanate (NDI), methylene biscyclohexyl isocyanate (HMDI) (hydrogenated MDI), MDI (especially 4,4'- and 4,2-MDI) and isophorone diisocyanate (IPDI), with MDI being particularly preferred.
[0062] In a preferred embodiment, the polyisocyanate used to prepare the OH-terminated prepolymer is MDI having a functionality of 2 or more, in particular of 2 to 3, particularly preferably of 2 to 2.3.
[0063] The total polyisocyanate content of Component B is preferably from 0.25 to 2.5% by weight, more preferably from 0.5 to 2% by weight, and particularly preferably from 1.2 to 1.6% by weight, based on the total weight of Component B.
[0064] In a preferred embodiment, component B comprises 0.25 to 2.5% by weight, more preferably 0.5 to 2% by weight, particularly preferably 1.2 to 1.6% by weight, of MDI having a functionality of 2 to 2.3, particularly preferably 2.2, based on the total weight of component B.
[0065] The polyisocyanate is preferably used at a 4:1 NCO equivalent to the OH groups in the polyol to ensure that the prepolymer is OH terminated.
[0066] Some examples of preferred OH-terminated prepolymer components are as follows: 1. Polyol: 25 to 40% by weight, more preferably 27 to 35% by weight, particularly preferably 32 to 34% by weight, of a poly(propylene oxide) triol having an equivalent weight of 1,500 to 1,700 g / eq, based on the total weight of component B; and Isocyanates: based on the total weight of component B, 0.25 to 2.5% by weight, more preferably 0.5 to 2% by weight, particularly preferably 1.2 to 1.6% by weight of MDI having a functionality of 2 to 2.3, particularly preferably 2.2 2. Polyol: 32-34 wt. % of a poly(propylene oxide) triol having an equivalent weight of 1,500-1,700 g / eq, based on the total weight of component B; and Isocyanates: 1.2 to 1.6 wt.-%, based on the total weight of component B, of MDI having a functionality of 2 to 2.3, particularly preferably 2.2.
[0067] Component B further comprises a catalyst capable of catalyzing the reaction of isocyanate groups with OH groups.
[0068] Examples of such catalysts include tertiary amine catalysts, organometallic catalysts such as bismuth catalysts, alkyltin carboxylates, oxides and tin mercaptides.
[0069] Specific examples of tertiary amine catalysts include N-methylmorpholine, N-methylimidazole, triethylenediamine, bis-(2-dimethylaminoethyl)-ether, 1,4-diazabicyclo[2.2.2]octane (DABCO), dimethylcyclohexylamine, dimethylethanolamine, 2,2-dimorpholinyl diethyl ether (DMDEE), N,N,N-dimethylaminopropylhexahydrotriazine, dimethyltetrahydropyrimidine, tetramethylethylenediamine, dimethylcyclohexylamine, 2,2-N,N-benzyldimethylamine, Examples of the diamine include dimethylethanolamine, dimethylaminopropylamine, pentadimethyldiethylenetriamine, N,N,N',N'-tetramethyl-1,6-hexanediamine, N,N',N'-trimethylaminoethylpiperazine, 1,1'-[[3-(dimethylamino)propyl]imino]bispropan-2-ol, 1,3,5-tris[3-(dimethylamino)propyl]hexahydro-1,3,5-triazine, N-N-dimethyldipropylenetriamine, and N,N,N'-trimethylaminoethylethanolamine, with DMDEE being particularly preferred.
[0070] When an organometallic catalyst is used, it is any organometallic catalyst capable of catalyzing the reaction between an isocyanate and a functional group having at least one reactive hydrogen. Examples include bismuth catalysts, metal carboxylates, such as tin carboxylates, zinc carboxylates, etc. Metal alkanoates include stannous octoate, bismuth octoate, or bismuth neodecanoate. Preferably, the at least one organometallic catalyst is a bismuth catalyst or an organotin catalyst. Examples include dibutyltin dilaurate, dimethyltin dineodecanoate, dimethyltin mercaptide, dimethyltin carboxylate, dimethyltin dioleate, dimethyltin dithioglycolate, dibutyltin mercaptide, dibutyltin bis(2-ethylhexylthioglycolate), dibutyltin sulfide, dioctyltin dithioglycolate, dioctyltin mercaptide, dioctyltin dioctoate, dioctyltin dineodecanoate, dioctyltin dilaurate. In a preferred embodiment, the catalyst is a tin catalyst, particularly preferably dioctyltin mercaptide and / or dimethyltin dithioglycolate. In a particularly preferred embodiment, the catalyst is a mixture of dioctyltin mercaptide and dimethyltin dithioglycolate.
[0071] The catalyst is preferably used in an amount of 0.02 to 0.12% by weight, more preferably 0.03 to 0.1% by weight, based on the total weight of component B.
[0072] In a preferred embodiment, the catalyst is dioctyltin mercaptide, used at 0.03 to 0.07% by weight, based on the total weight of component B, and dimethyltin dithioglycolate, used at 0.001 to 0.003% by weight, based on the total weight of component B.
[0073] Component B may further comprise an adhesion promoter, which is preferably a reactive silane.
[0074] The reactive silane is any silane that contains a mercapto group, a primary or secondary amine group, or a hydrolyzable silylalkoxy group covalently bonded to an epoxy group.
[0075] In a particularly preferred embodiment, the reactive silane is an epoxy silane.Preferably, the epoxy silane is selected from glycidyloxyalkyl(trialkoxy)silane and glycidyloxyalkyl(methyl-dialkoxy)silane.Examples of suitable epoxy silanes include tris(diethylene glycol methyl ether)silyl propylene glycidyl ether, (3-glycidyloxypropyl)trimethoxysilane, (3-glycidyloxypropyl)triethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 2-(3,4-epoxycyclohexyl)-ethyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)-ethyltriethoxysilane, with (3-glycidyloxypropyl)trimethoxysilane being particularly preferred.
[0076] If used, the reactive silane is preferably present in Component B at 0.1 to 1 wt. %, more preferably 0.25 to 0.75 wt. %, and especially preferably 0.4 to 0.6 wt. %, based on the total weight of Component B.
[0077] In a preferred embodiment, Component B contains, based on the total weight of Component B, 0.1 to 1 wt %, more preferably 0.25 to 0.75 wt %, and particularly preferably 0.4 to 0.6 wt % of glycidyloxypropyl)trimethoxysilane.
[0078] Component B may further comprise a diol or triol having a molecular weight of less than 200 Da, such as butanediol or glycerin, with butanediol being particularly preferred.
[0079] If used, the diol or triol having a molecular weight of less than 200 Da is preferably present at 3 to 9 wt. %, more preferably 4 to 7 wt. %, based on the total weight of component B.
[0080] In a preferred embodiment, Component B comprises 3 to 9 wt. %, more preferably 4 to 7 wt. %, of 1,4-butanediol, based on the total weight of Component B.
[0081] The OH-terminated prepolymer of component B is prepared by mixing at least one polyol with at least one polyisocyanate, preferably under vacuum, at a temperature in the range of 30-50°C, more preferably 32-40°C.
[0082] If used, the remaining ingredients of Component B, such as fillers, adhesion promoters, catalysts, are added to the prepolymer and mixed until uniform, then Component B is stored in a moisture-proof container.
[0083] Filler Component A and / or Component B may comprise the following fillers: Aluminum trihydroxide having a multimodal particle size distribution; Graphite having a spherical particle shape, and Graphite having an aspect ratio of greater than 2; As a result, when component A and component B are mixed together to form the adhesive mixture, the adhesive mixture contains greater than 40% by weight aluminum trihydroxide and greater than 8% by weight graphite.
[0084] The term multimodal particle size distribution means that at least two major peaks are observed when particle size is plotted with particle size on the x-axis and volume % on the y-axis.
[0085] In a preferred embodiment, the aluminum trihydroxide is bimodal.
[0086] The particle size distribution of aluminum trihydroxide is typically measured using laser diffraction, using water containing sodium pyrophosphate as the suspending agent.
[0087] In a preferred embodiment, the aluminum trihydroxide has the following particle size distribution: 1 to 20% by volume is less than 1 μm, 10 to 30% by volume is 1 to 10 μm, 5 to 30% by volume is 10 to 20 μm, more than 10% by volume is 20 to 50 μm, and more than 20% by volume is 50 to 100 μm.
[0088] In a more preferred embodiment, the aluminum trihydroxide has the following particle size distribution: 1-10% by volume is less than 1 μm, 5-20% by volume is 1-10 μm, 6-20% by volume is 10-20 μm, 5-40% by volume is 20-50 μm, and 35-60% by volume is 50-100 μm.
[0089] In a more particularly preferred embodiment, the aluminum trihydroxide has the following particle size distribution: 1-5% by volume is less than 1 μm, 5-15% by volume is 1-10 μm, 6-15% by volume is 10-20 μm, 20-40% by volume is 20-50 μm, and 40-70% by volume is 50-100 μm.
[0090] Alternatively, the aluminum trihydroxide has the following particle size distribution: 1 to 20% by weight is less than 1 μm, 5 to 30% by weight is 1 to 10 μm, 3 to 30% by weight is 10 to 20 μm, more than 10% by weight is 20 to 50 μm, and more than 35% by weight is 50 to 100 μm.
[0091] More preferably, the aluminum trihydroxide has the following particle size distribution: 1 to 10% by weight is less than 1 μm, 5 to 20% by weight is 1 to 10 μm, 3 to 20% by weight is 10 to 20 μm, 10 to 40% by weight is 20 to 50 μm, and 35 to 70% by weight is 50 to 100 μm.
[0092] More particularly preferably, the aluminum trihydroxide has the following particle size distribution: 1 to 5% by weight is less than 1 μm, 5 to 15% by weight is 1 to 10 μm, 5 to 15% by weight is 10 to 20 μm, 15 to 35% by weight is 20 to 50 μm, and 40 to 60% by weight is 50 to 100 μm.
[0093] In a preferred embodiment, the aluminum trihydroxide is D 90~120μm90 , more preferably 95 to 105 μm D 90 and aluminum trihydroxide having the formula D of 15 to 25 μm, preferably 18 to 21 μm 90 and a mixture of aluminum trihydroxide having the formula:
[0094] In another preferred embodiment, the aluminum trihydroxide is D 95~105μm 90 and aluminum trihydroxide having the formula D 18~21μm 90 and a mixture of aluminum trihydroxide having the formula:
[0095] In another preferred embodiment, the aluminum trihydroxide is D 90~120μm 90 , more preferably 95 to 105 μm D 90 , and D of 45 to 55 μm 50 , more preferably 48 to 52 μm D 50 and aluminum trihydroxide having the formula D of 15 to 25 μm, preferably 18 to 21 μm 90 , and D of 5 to 10 μm 50 , more preferably 6 to 9 μm D 50 and a mixture of aluminum trihydroxide having the formula:
[0096] In another preferred embodiment, the aluminum trihydroxide is D 90~120μm 90 , more preferably 95 to 105 μm D 90 , 45-55μm D 50 , more preferably 48 to 52 μm D 50 , and 8 to 12 μm, more preferably 9 to 11 μm D 10 and aluminum trihydroxide having the formula D of 15 to 25 μm, preferably 18 to 21 μm 90 , and D of 5 to 10 μm 50 , more preferably 6 to 9 μm D 50and a mixture of aluminum trihydroxide having the formula:
[0097] In a preferred embodiment, the aluminum trihydroxide comprises, based on the total amount of aluminum trihydroxide: D 90~120μm 90 , more preferably 95 to 105 μm D 90 80 to 95% by weight of aluminum trihydroxide having the formula: D of 15 to 25 μm, preferably 18 to 21 μm 90 5 to 20% by weight of aluminum trihydroxide having It comprises or consists of a mixture of
[0098] In another preferred embodiment, the aluminum trihydroxide is, based on the total amount of aluminum trihydroxide, D 95~105μm 90 80 to 95% by weight of aluminum trihydroxide having the formula: D 18~21μm 90 5 to 20% by weight of aluminum trihydroxide having It comprises or consists of a mixture of
[0099] In another preferred embodiment, the aluminum trihydroxide is, based on the total amount of aluminum trihydroxide, D 90~120μm 90 , more preferably 95 to 105 μm D 90 , and D of 45 to 55 μm 50 , more preferably 48 to 52 μm D 50 80 to 95% by weight of aluminum trihydroxide having the formula: D of 15 to 25 μm, preferably 18 to 21 μm 90 , and D of 5 to 10 μm 50 , more preferably 6 to 9 μm D 50 5 to 20% by weight of aluminum trihydroxide having It comprises or consists of a mixture of
[0100] In another preferred embodiment, the aluminum trihydroxide is, based on the total amount of aluminum trihydroxide, D 90~120μm 90 , more preferably 95 to 105 μm D 90 , 45-55μm D 50 , more preferably 48 to 52 μm D 50 , and 8 to 12 μm, more preferably 9 to 11 μm D 10 80 to 95% by weight of aluminum trihydroxide having the formula: D of 15 to 25 μm, preferably 18 to 21 μm 90 , and D of 5 to 10 μm 50 , more preferably 6 to 9 μm D 50 5 to 20% by weight of aluminum trihydroxide having It comprises or consists of a mixture of
[0101] ATH may be present in component A, component B or both. Preferably, both component A and component B contain ATH.
[0102] In a preferred embodiment, Component A contains 40 to 60% by weight of ATH, more preferably 45 to 55% by weight of ATH, based on the total weight of Component A.
[0103] In a preferred embodiment, Component B contains 40 to 60% by weight of ATH, more preferably 45 to 55% by weight of ATH, based on the total weight of Component B.
[0104] In another preferred embodiment, component A contains 40 to 60% by weight, more preferably 45 to 55% by weight, of ATH, based on the total weight of component A, and component B contains 40 to 60% by weight, more preferably 45 to 55% by weight, of ATH, based on the total weight of component B.
[0105] Component A and / or Component B comprise graphite having a spherical particle shape. In this specification, "spherical" means particles having an aspect ratio of 0.8 to 1.2, more preferably 0.9 to 1.1.
[0106] The spherical graphite has a D of preferably 5 to 50 μm, more preferably 10 to 20 μm, and particularly preferably 15 to 16.2 μm. 50 has.
[0107] The spherical graphite has a D of preferably 30 to 60 μm, more preferably 35 to 50 μm, and particularly preferably 40 to 48 μm. 90 has.
[0108] The spherical graphite has a D of preferably 5 to 50 μm, more preferably 10 to 20 μm, and particularly preferably 15 to 16.2 μm. 50 and D of 30 to 60 μm, more preferably 35 to 50 μm, particularly preferably 40 to 48 μm. 90 has.
[0109] The spherical graphite is preferably 1 to 20 mm. 2 / g, more preferably 5 to 15m 2 / g, particularly preferably 9m 2 / g BET surface area.
[0110] The spherical graphite has a D of preferably 5 to 50 μm, more preferably 10 to 20 μm, and particularly preferably 15 to 16.2 μm. 50 , and 1 to 20 m 2 / g, more preferably 5 to 15m 2 / g, particularly preferably 9m 2 / g BET surface area.
[0111] The spherical graphite has a D of preferably 30 to 60 μm, more preferably 35 to 50 μm, and particularly preferably 40 to 48 μm. 90 , and 1 to 20 m 2 / g, more preferably 5 to 15m 2 / g, particularly preferably 9m 2 / g BET surface area.
[0112] The spherical graphite has a D of preferably 5 to 50 μm, more preferably 10 to 20 μm, and particularly preferably 15 to 16.2 μm.50 and D of 30 to 60 μm, more preferably 35 to 50 μm, particularly preferably 40 to 48 μm. 90 , and 1 to 20 m 2 / g, more preferably 5 to 15m 2 / g, particularly preferably 9m 2 / g BET surface area.
[0113] The spherical graphite may be present in component A, component B or both. Preferably, both component A and component B contain spherical graphite.
[0114] In a preferred embodiment, Component A contains spherical graphite in an amount of 2 to 15% by weight, more preferably 4 to 8% by weight, based on the total weight of Component A.
[0115] In a preferred embodiment, Component B contains spherical graphite in an amount of 5 to 20% by weight, more preferably 8 to 12% by weight, based on the total weight of Component B.
[0116] In another preferred embodiment, component A contains 2 to 15% by weight, more preferably 4 to 8% by weight, of spherical graphite, based on the total weight of component A, and component B contains 5 to 20% by weight, more preferably 8 to 12% by weight, of spherical graphite, based on the total weight of component B.
[0117] Component A and / or component B comprises graphite having an aspect ratio of more than 2, more preferably more than 3, particularly preferably more than 4. The graphite having an aspect ratio of more than 2 is preferably selected from graphite particles, graphene platelets and mixtures thereof.
[0118] In a preferred embodiment, the graphite having an aspect ratio of greater than 2 has a D of 80 to 110 μm, more preferably 85 to 95 μm. 90 The graphite particles have the following structure:
[0119] In another preferred embodiment, the graphite having an aspect ratio of more than 2 is a graphene nanoplatelet having a thickness of 10 to 30 nm, more preferably 16 to 20 nm, and an average particle size of 10 to 35 μm, more preferably 15 to 30 μm, particularly preferably 24 to 26 μm.
[0120] Graphite having an aspect ratio greater than 2 may be present in component A, component B or both. Preferably, both component A and component B contain graphite having an aspect ratio greater than 2.
[0121] In a preferred embodiment, Component A contains 0.5 to 2.5 wt. %, more preferably 0.75 to 2 wt. %, and particularly preferably 0.0 to 1.3 wt. %, of graphite having an aspect ratio greater than 2, based on the total weight of Component A.
[0122] In a preferred embodiment, Component B contains 0.5 to 2.5 wt. %, more preferably 0.75 to 2 wt. %, and particularly preferably 0.0 to 1.3 wt. %, of graphite having an aspect ratio greater than 2, based on the total weight of Component B.
[0123] In another preferred embodiment, component A contains 0.5 to 2.5 wt. %, more preferably 0.75 to 2 wt. %, and particularly preferably 0.0 to 1.3 wt. %, of graphite having an aspect ratio greater than 2, based on the total weight of component A, and component B contains 0.5 to 2.5 wt. %, more preferably 0.75 to 2 wt. %, and particularly preferably 0.0 to 1.3 wt. %, of graphite having an aspect ratio greater than 2, based on the total weight of component B.
[0124] In a preferred embodiment, component A and / or component B comprises the following combination of fillers: 1. D 90~120μm 90 , more preferably 95 to 105 μm D 90 and aluminum trihydroxide having the formula D of 15 to 25 μm, preferably 18 to 21 μm 90ATH comprising or consisting of a mixture with aluminum trihydroxide having Spherical graphite, and Graphite with an aspect ratio greater than 2 2. D 95~105μm 90 and aluminum trihydroxide having the formula D 18~21μm 90 ATH comprising or consisting of a mixture with aluminum trihydroxide having Spherical graphite, and Graphite with an aspect ratio greater than 2 3. D 90~120μm 90 , more preferably 95 to 105 μm D 90 , and D of 45 to 55 μm 50 , more preferably 48 to 52 μm D 50 and aluminum trihydroxide having the formula D of 15 to 25 μm, preferably 18 to 21 μm 90 , and D of 5 to 10 μm 50 , more preferably 6 to 9 μm D 50 ATH comprising or consisting of a mixture with aluminum trihydroxide having Spherical graphite, and Graphite with an aspect ratio greater than 2 4. D 90~120μm 90 , more preferably 95 to 105 μm D 90 , 45-55μm D 50 , more preferably 48 to 52 μm D 50 , and 8 to 12 μm, more preferably 9 to 11 μm D 10 and aluminum trihydroxide having the formula D of 15 to 25 μm, preferably 18 to 21 μm 90 , and D of 5 to 10 μm 50 , more preferably 6 to 9 μm D 50 ATH comprising or consisting of a mixture with aluminum trihydroxide having Spherical graphite, and Graphite with an aspect ratio greater than 2 5. Based on the total amount of aluminum trihydroxide, D 90~120μm 90 , more preferably 95 to 105 μm D 90 80 to 95% by weight of aluminum trihydroxide having the formula: D of 15 to 25 μm, preferably 18 to 21 μm 90 ATH comprising or consisting of a mixture of 5 to 20% by weight of aluminum trihydroxide having the formula: Spherical graphite, and Graphite with an aspect ratio greater than 2 6. Based on the total amount of aluminum trihydroxide, D 95~105μm 90 80 to 95% by weight of aluminum trihydroxide having the formula: D 18~21μm 90 ATH comprising or consisting of a mixture of 5 to 20% by weight of aluminum trihydroxide having the formula: Spherical graphite, and Graphite with an aspect ratio greater than 2 7. Based on the total amount of aluminum trihydroxide, D 90~120μm 90 , more preferably 95 to 105 μm D 90 , and D of 45 to 55 μm 50 , more preferably 48 to 52 μm D 50 80 to 95% by weight of aluminum trihydroxide having the formula: D of 15 to 25 μm, preferably 18 to 21 μm 90 , and D of 5 to 10 μm 50 , more preferably 6 to 9 μm D 50 ATH comprising or consisting of a mixture of 5 to 20% by weight of aluminum trihydroxide having the formula: Spherical graphite, and Graphite with an aspect ratio greater than 2 8. Based on the total amount of aluminum trihydroxide, D 90~120μm90 , more preferably 95 to 105 μm D 90 , 45-55μm D 50 , more preferably 48 to 52 μm D 50 , and 8 to 12 μm, more preferably 9 to 11 μm D 10 80 to 95% by weight of aluminum trihydroxide having the formula: D of 15 to 25 μm, preferably 18 to 21 μm 90 , and D of 5 to 10 μm 50 , more preferably 6 to 9 μm D 50 ATH comprising or consisting of a mixture of 5 to 20% by weight of aluminum trihydroxide having the formula: Spherical graphite, and Graphite with an aspect ratio greater than 2 9. D 90~120μm 90 , more preferably 95 to 105 μm D 90 and aluminum trihydroxide having the formula D of 15 to 25 μm, preferably 18 to 21 μm 90 and aluminum trihydroxide having the formula D of 5 to 50 μm, more preferably 10 to 20 μm, particularly preferably 15 to 16.2 μm 50 ATH comprising or consisting of a mixture of spherical graphite having Graphite with an aspect ratio greater than 2 10. D 95~105μm 90 and aluminum trihydroxide having the formula D 18~21μm 90 and aluminum trihydroxide having the formula D of 5 to 50 μm, more preferably 10 to 20 μm, particularly preferably 15 to 16.2 μm 50 ATH comprising or consisting of a mixture of spherical graphite having Graphite with an aspect ratio greater than 2 11. D 90~120μm 90 , more preferably 95 to 105 μm D90 , and D of 45 to 55 μm 50 , more preferably 48 to 52 μm D 50 and aluminum trihydroxide having the formula D of 15 to 25 μm, preferably 18 to 21 μm 90 , and D of 5 to 10 μm 50 , more preferably 6 to 9 μm D 50 ATH comprising or consisting of a mixture with aluminum trihydroxide having D of 5 to 50 μm, more preferably 10 to 20 μm, particularly preferably 15 to 16.2 μm 50 Spherical graphite having the formula: Graphite with an aspect ratio greater than 2 12. D 90~120μm 90 , more preferably 95 to 105 μm D 90 , 45-55μm D 50 , more preferably 48 to 52 μm D 50 , and 8 to 12 μm, more preferably 9 to 11 μm D 10 and aluminum trihydroxide having the formula D of 15 to 25 μm, preferably 18 to 21 μm 90 , and D of 5 to 10 μm 50 , more preferably 6 to 9 μm D 50 ATH comprising or consisting of a mixture with aluminum trihydroxide having D of 5 to 50 μm, more preferably 10 to 20 μm, particularly preferably 15 to 16.2 μm 50 Spherical graphite having the formula: Graphite with an aspect ratio greater than 2 13. Based on the total amount of aluminum trihydroxide, D 90~120μm 90 , more preferably 95 to 105 μm D 90 80 to 95% by weight of aluminum trihydroxide having the formula: D of 15 to 25 μm, preferably 18 to 21 μm 90ATH comprising or consisting of a mixture of 5 to 20% by weight of aluminum trihydroxide having the formula: D of 5 to 50 μm, more preferably 10 to 20 μm, particularly preferably 15 to 16.2 μm 50 Spherical graphite having the formula: Graphite with an aspect ratio greater than 2 14. Based on the total amount of aluminum trihydroxide, D 95~105μm 90 80 to 95% by weight of aluminum trihydroxide having the formula: D 18~21μm 90 ATH comprising or consisting of a mixture of 5 to 20% by weight of aluminum trihydroxide having the formula: D of 5 to 50 μm, more preferably 10 to 20 μm, particularly preferably 15 to 16.2 μm 50 Spherical graphite having the formula: Graphite with an aspect ratio greater than 2 15. Based on the total amount of aluminum trihydroxide, D 90~120μm 90 , more preferably 95 to 105 μm D 90 , and D of 45 to 55 μm 50 , more preferably 48 to 52 μm D 50 80 to 95% by weight of aluminum trihydroxide having the formula: D of 15 to 25 μm, preferably 18 to 21 μm 90 , and D of 5 to 10 μm 50 , more preferably 6 to 9 μm D 50 ATH comprising or consisting of a mixture of 5 to 20% by weight of aluminum trihydroxide having the formula: D of 5 to 50 μm, more preferably 10 to 20 μm, particularly preferably 15 to 16.2 μm 50 Spherical graphite having the formula: Graphite with an aspect ratio greater than 2 16. Based on the total amount of aluminum trihydroxide, D 90~120μm 90 , more preferably 95 to 105 μm D90 , 45-55μm D 50 , more preferably 48 to 52 μm D 50 , and 8 to 12 μm, more preferably 9 to 11 μm D 10 80 to 95% by weight of aluminum trihydroxide having the formula: D of 15 to 25 μm, preferably 18 to 21 μm 90 , and D of 5 to 10 μm 50 , more preferably 6 to 9 μm D 50 ATH comprising or consisting of a mixture of 5 to 20% by weight of aluminum trihydroxide having the formula: D of 5 to 50 μm, more preferably 10 to 20 μm, particularly preferably 15 to 16.2 μm 50 Spherical graphite having the formula: Graphite with an aspect ratio greater than 2 17. ATH having a bimodal particle size distribution, and Spherical graphite, and Graphite with an aspect ratio greater than 2 18. ATH having a bimodal particle size distribution, and D of 5 to 50 μm, more preferably 10 to 20 μm, particularly preferably 15 to 16.2 μm 50 Spherical graphite having the formula: Graphite with an aspect ratio greater than 2 19. ATH having a particle size distribution of 1-20% by volume less than 1 μm, 10-30% by volume 1-10 μm, 5-30% by volume 10-20 μm, more than 10% by volume 20-50 μm, and more than 20% by volume 50-100 μm; and Spherical graphite, and Graphite with an aspect ratio greater than 2 20. ATH having a particle size distribution of 1-20% by volume less than 1 μm, 10-30% by volume 1-10 μm, 5-30% by volume 10-20 μm, more than 10% by volume 20-50 μm, and more than 20% by volume 50-100 μm; and D of 5 to 50 μm, more preferably 10 to 20 μm, particularly preferably 15 to 16.2 μm 50Spherical graphite having the formula: Graphite with an aspect ratio greater than 2
[0125] The combination of fillers may be present in Component A, Component B or both. Preferably, both Component A and Component B contain a combination of fillers.
[0126] In a preferred embodiment, Component A comprises 45-75% by weight total filler, more preferably 50-60% by weight total filler, based on the total weight of Component A.
[0127] In a preferred embodiment, Component B comprises 45-75% by weight total filler, more preferably 50-60% by weight total filler, based on the total weight of Component B.
[0128] In a preferred embodiment, Component A comprises 45-75% by weight total filler, more preferably 50-60% by weight total filler, based on the total weight of Component A, and Component B comprises 45-75% by weight total filler, more preferably 50-60% by weight total filler, based on the total weight of Component B.
[0129] Manufacturing method The adhesive composition of the present invention is made by mixing the ingredients of each component separately, preferably under inert and dry conditions and / or under vacuum, until a homogenous mixture is obtained. Once components A and B are mixed, they are stored in separate containers until use.
[0130] How to use In one aspect, the present invention provides a method for bonding two or more substrates, comprising the steps of: (1) A two-component thermally conductive polyurethane adhesive, A. a first component (isocyanate) comprising an NCO-terminated prepolymer made by reacting at least one polyol with at least one polyisocyanate; B. are bonded together using a cured adhesive produced by mixing and curing a second component (polyol) that contains an OH-terminated prepolymer made by reacting at least one polyol with at least one polyisocyanate and a catalyst capable of catalyzing the reaction of isocyanate groups with OH groups; Component A and / or Component B may comprise the following fillers: Aluminum trihydroxide having a particle size distribution of 1 to 20% by volume less than 1 μm, 5 to 30% by volume 1 to 10 μm, 5 to 30% by volume 10 to 20 μm, more than 5% by volume 20 to 50 μm, and more than 30% by volume 50 to 100 μm; Graphite having a spherical particle shape, and Graphite having an aspect ratio of greater than 2; As a result, a two-part thermally conductive polyurethane adhesive is provided, whereby when component A and component B are mixed together to form the adhesive mixture, the adhesive mixture comprises greater than 40% by weight aluminum trihydroxide and greater than 8% by weight graphite; (2) mixing the first component and the second component to obtain an adhesive mixture; (3) applying the adhesive mixture to a first substrate; (4) placing the first substrate in adhesive contact with a second substrate; (5) curing the adhesive mixture.
[0131] The ingredients of Components A and B useful in the method of the present invention are as described for the adhesive.
[0132] Mixing is accomplished by any method that can achieve a homogenous mixture fairly quickly. Typically, mixing is accomplished by simultaneously dispensing both components into a mixing vessel or channel. Mixing of components A and B can be in any desired ratio, but is typically accomplished using a volume ratio A:B of 0.8 to 1.2, more preferably 1:1.
[0133] The application of the adhesive mixture to the substrate is typically done manually (automatically) using a suitable application gun and a static mixer. The adhesive is loaded into a cartridge that ensures the correct mix ratio (in this case 1:1). The cartridge is placed in the application gun and a suitable static mixer is attached. The adhesive is then pressed against the surface to be bonded through the static mixer.
[0134] Curing is typically carried out at ambient temperature (eg, 23° C.) and humidity (eg, 50% relative humidity). Full cure with the adhesives of the present invention usually occurs in 7-10 days.
[0135] Substrates include, but are not limited to, metals, plastics, etc. The adhesives of the present invention are particularly suitable for bonding e-coated metals, acrylate coated surfaces, laser treated metals (aluminum), nickel plated steel, plasma pre-treated PET.
[0136] Preferred applications include thermally conductive materials for use in the automotive industry for thermal management of EV batteries, particularly for bonding modules or cells to cooling plates, as well as any application where a thermally conductive material is required.
[0137] [Effects of the invention] The cured adhesives of the present invention (7 days, 23° C., 50% RH) preferably exhibit a thermal conductivity of at least 1 W / mK, more preferably at least 1.1 W / mK, and most preferably at least 1.2 W / mK. Thermal conductivity is measured according to ASTM 5470, as described in the examples.
[0138] The cured adhesives of the present invention (7 days, 23° C., 50% RH) preferably exhibit an elongation at break of 20% or more, more preferably greater than 23%, which allows for bonding of materials with different thermal expansion coefficients. The elongation at break is measured according to ISO EN 572-2, where the material is tested after full curing at a speed of 10 mm / min.
[0139] The cured adhesives of the present invention (7 days, 23° C., 50% RH) preferably exhibit a UL94 flame rating of V1 or greater.
[0140] The cured adhesive of the present invention (7 days, 23° C., 50% RH) preferably has a viscosity of 10 10 Ωm or more, more preferably 10 11 It exhibits a volume resistivity of Ωm or more.
[0141] The adhesives of the present invention exhibit low wear, which means less need to replace dispensing and mixing equipment.
[0142] Particularly preferred embodiments The following are particularly preferred embodiments of the adhesive composition of the present invention.
[0143] 1. A two-part thermally conductive polyurethane adhesive comprising: A. a first component (isocyanate) comprising an NCO-terminated prepolymer made by reacting at least one polyol with at least one polyisocyanate; B. A second component (polyol) comprising an OH-terminated prepolymer made by reacting at least one polyol with at least one polyisocyanate and a catalyst capable of catalyzing the reaction of isocyanate groups with OH groups; Component A and / or Component B may comprise the following fillers: aluminium trihydroxide having a multimodal (preferably bimodal) particle size distribution; Graphite having a spherical particle shape, and Graphite having an aspect ratio of greater than 2; As a result, a two-part thermally conductive polyurethane adhesive, whereby when component A and component B are mixed together to form the adhesive mixture, the adhesive mixture comprises greater than 40% by weight aluminum trihydroxide and greater than 8% by weight graphite.
[0144] 2. A kit for making an adhesive mixture, comprising: A. a first component (isocyanate) comprising an NCO-terminated prepolymer made by reacting at least one polyol with at least one polyisocyanate; B. A second component (polyol) comprising an OH-terminated prepolymer made by reacting at least one polyol with at least one polyisocyanate and a catalyst capable of catalyzing the reaction of isocyanate groups with OH groups; Component A and / or Component B may comprise the following fillers: aluminium trihydroxide having a multimodal (preferably bimodal) particle size distribution; Graphite having a spherical particle shape, and Graphite having an aspect ratio of greater than 2; As a result, when component A and component B are mixed together to form the adhesive mixture, the adhesive mixture comprises greater than 40% by weight aluminum trihydroxide and greater than 8% by weight graphite.
[0145] 3. A method for bonding two or more substrates, comprising: (1) A two-component thermally conductive polyurethane adhesive, A. a first component (isocyanate) comprising an NCO-terminated prepolymer made by reacting at least one polyol with at least one polyisocyanate; B. are bonded together using a cured adhesive produced by mixing and curing a second component (polyol) that contains an OH-terminated prepolymer made by reacting at least one polyol with at least one polyisocyanate and a catalyst capable of catalyzing the reaction of isocyanate groups with OH groups; Component A and / or Component B may comprise the following fillers: aluminium trihydroxide having a multimodal (preferably bimodal) particle size distribution; Graphite having a spherical particle shape, and Graphite having an aspect ratio of greater than 2; As a result, a two-part thermally conductive polyurethane adhesive is provided, whereby when component A and component B are mixed together to form the adhesive mixture, the adhesive mixture comprises greater than 40% by weight aluminum trihydroxide and greater than 8% by weight graphite; (2) mixing the first component and the second component to obtain an adhesive mixture; (3) applying the adhesive mixture to a first substrate; (4) placing the first substrate in adhesive contact with a second substrate; (5) curing the adhesive mixture.
[0146] 4. An adhesive assembly comprising: (1) a first substrate; (2) a second substrate; The first substrate and the second substrate are A. a first component (isocyanate) comprising an NCO-terminated prepolymer made by reacting at least one polyol with at least one polyisocyanate; B. are bonded together using a cured adhesive produced by mixing and curing a second component (polyol) that contains an OH-terminated prepolymer made by reacting at least one polyol with at least one polyisocyanate and a catalyst capable of catalyzing the reaction of isocyanate groups with OH groups; Component A and / or Component B may comprise the following fillers: aluminium trihydroxide having a multimodal (preferably bimodal) particle size distribution; Graphite having a spherical particle shape, and Graphite having an aspect ratio of greater than 2; As a result, an adhesive assembly, when component A and component B are mixed together to form an adhesive mixture, the adhesive mixture comprises greater than 40% by weight aluminum trihydroxide and greater than 8% by weight graphite.
[0147] 5. Any one of embodiments 1-4, wherein at least one polyol used to make the NCO-terminated prepolymer is a polyether polyol.
[0148] 6. Any one of the preceding embodiments, wherein at least one polyol used to prepare the NCO-terminated prepolymer is selected from polyols having a functionality of 2 or greater, more preferably 2-3.
[0149] 7. Any one of embodiments 1-6, wherein at least one polyol used to make the NCO-terminated prepolymer has a functionality of 2.
[0150] 8. Any one of the preceding embodiments, wherein the polyol used to prepare the NCO-terminated prepolymer is selected from poly(C2-C4-alkylene oxide) polyols, in particular poly(ethylene oxide) polyols, poly(propylene oxide) polyols, poly(tetramethylene oxide) polyols, and mixtures thereof.
[0151] 9. Any one of embodiments 1-8, wherein the polyol used to make the NCO-terminated prepolymer is a poly(propylene oxide) polyol.
[0152] 10. Any one of embodiments 1-9, wherein the polyol used to make the NCO-terminated prepolymer is selected from poly(propylene oxide) polyols having a functionality of 2-3.
[0153] 11. Any one of embodiments 1-10, wherein at least one polyol used to make the NCO-terminated prepolymer has a molecular weight of 400 to 2,500 Da.
[0154] 12. Any one of embodiments 1-11, wherein at least one polyol used to make the NCO-terminated prepolymer preferably has an average equivalent weight of 200 to 1,250 g / eq, more preferably 210 to 520 g / eq.
[0155] 13. Any one of embodiments 1-12, wherein at least one polyol used to make the NCO-terminated prepolymer is a mixture of polyols.
[0156] 14. Any one of the preceding embodiments, wherein at least one polyol used to make the NCO-terminated prepolymer is a mixture of polyols including a polyol having an average equivalent weight of 200-250 g / eq and a polyol having an average equivalent weight of 475-550 g / eq.
[0157] 15. Any one of embodiments 1-14, wherein at least one polyol used to make the NCO-terminated prepolymer is a mixture of a poly(propylene oxide)-based polyol having an average equivalent weight of 200-250 g / eq and a poly(propylene oxide)-based polyol having an average equivalent weight of 475-550 g / eq.
[0158] 16. Any one of the preceding embodiments, wherein at least one polyol used to make the NCO-terminated prepolymer is a mixture of a poly(propylene oxide)-based diol having an average equivalent weight of 200-250 g / eq and a poly(propylene oxide)-based diol having an average equivalent weight of 475-550 g / eq.
[0159] 17. Any one of embodiments 1-16, wherein at least one polyol used to make the NCO-terminated prepolymer comprises a poly(propylene oxide)-based polyol (P1) having an average equivalent weight of 200-250 g / eq and a poly(propylene oxide)-based polyol (P2) having an average equivalent weight of 475-550 g / eq, and the ratio of P1:P2 is 0.35-0.55, more preferably 0.43-0.47.
[0160] 18. Any one of embodiments 1 to 17, wherein at least one polyol used to make the NCO-terminated prepolymer is a mixture of a poly(propylene oxide)-based diol (P1) having an average equivalent weight of 200 to 250 g / eq and a poly(propylene oxide)-based diol (P2) having an average equivalent weight of 475 to 550 g / eq, the ratio of P1:P2 being 0.35 to 0.55, more preferably 0.43 to 0.47.
[0161] 19. Any one of embodiments 1 to 18, wherein the total polyol content in the NCO-terminated prepolymer is 9 to 20 wt.-%, more preferably 10 to 15 wt.-%, and particularly preferably 12 to 14 wt.-%, based on the total weight of component A.
[0162] 20. Any one of the preceding embodiments, wherein component A comprises 2 to 10% by weight, more preferably 3 to 6% by weight, and more particularly preferably 4 to 5% by weight of a poly(propylene oxide) diol having an equivalent weight of 200 to 250 g / eq.
[0163] 21. Any one of embodiments 1 to 20, wherein component A comprises 6 to 15 wt.%, more preferably 8 to 12 wt.%, and particularly preferably 9 to 10 wt.%, of a poly(propylene oxide)-based diol having an average equivalent weight of 475 to 550 g / eq.
[0164] 22. Any one of embodiments 1 to 21, wherein component A comprises 2 to 10 wt.-%, more preferably 3 to 6 wt.-%, more particularly preferably 4 to 5 wt.-%, of a poly(propylene oxide) diol having an equivalent weight of 200 to 250 g / eq, and component A comprises 6 to 15 wt.-%, more preferably 8 to 12 wt.-%, particularly preferably 9 to 10 wt.-%, of a poly(propylene oxide)-based diol having an average equivalent weight of 475 to 550 g / eq.
[0165] 23. Any one of embodiments 1 to 22, wherein component A comprises 2 to 10 wt.-%, more preferably 3 to 6 wt.-%, more particularly preferably 4 to 5 wt.-% of poly(propylene oxide) diol (P1) having an equivalent weight of 200 to 250 g / eq, and component A comprises 6 to 15 wt.-%, more preferably 8 to 12 wt.-%, particularly preferably 9 to 10 wt.-% of poly(propylene oxide)-based diol (P2) having an average equivalent weight of 475 to 550 g / eq, and the ratio of P1:P2 is 0.35 to 0.55, more preferably 0.43 to 0.47.
[0166] 24. Any one of embodiments 1-23, wherein at least one polyisocyanate used to make the NCO-terminated prepolymer is aromatic.
[0167] 25. Any one of the preceding embodiments, wherein the at least one polyisocyanate used to prepare the NCO-terminated prepolymer is selected from toluene diisocyanate (TDI), hexamethylene diisocyanate (HDI), naphthalene diisocyanate (NDI), methylene bis-cyclohexyl isocyanate (HMDI) (hydrogenated MDI), MDI (especially 4,4'- and 4,2-MDI) and isophorone diisocyanate (IPDI), and mixtures thereof.
[0168] 26. Any one of the preceding embodiments, wherein at least one polyisocyanate used to make the NCO-terminated prepolymer is MDI.
[0169] 27. Any one of the preceding embodiments, wherein at least one polyisocyanate used to prepare the NCO-terminated prepolymer is an MDI having a functionality of 2 or more, in particular a functionality of 2 to 3.
[0170] 28. Any one of the preceding embodiments, wherein at least one polyisocyanate used to prepare the NCO-terminated prepolymer is a mixture of MDI having a functionality of 2 to 2.3 and MDI having a functionality of 2.5 to 3, in particular a mixture of MDI having a functionality of 2.2 and MDI having a functionality of 2.7.
[0171] 29. Any one of embodiments 1 to 28, wherein the total polyisocyanate content of component A is 20 to 40% by weight, more preferably 25 to 35% by weight, and particularly preferably 28 to 32% by weight, based on the total weight of component A.
[0172] 30. Any one of the preceding embodiments, wherein component A comprises 25 to 35% by weight, more preferably 28 to 32% by weight, particularly preferably 30 to 31% by weight, of MDI having a functionality of 2 to 2.3, particularly preferably 2.2, based on the total weight of component A.
[0173] 31. Any one of embodiments 1 to 30, wherein component A comprises 0.25 to 1 wt.-%, more preferably 0.3 to 0.8 wt.-%, particularly preferably 0.5 to 0.7 wt.-%, of MDI having a functionality of 2.5 to 3, particularly preferably 2.7, based on the total weight of component A.
[0174] 32. Any one of embodiments 1 to 31, wherein component A comprises 25 to 35% by weight, more preferably 28 to 32% by weight, particularly preferably 30 to 31% by weight, based on the total weight of component A, of MDI having a functionality of 2 to 2.3, particularly preferably 2.2, and 0.25 to 1% by weight, more preferably 0.3 to 0.8% by weight, particularly preferably 0.5 to 0.7% by weight, based on the total weight of component A, of MDI having a functionality of 2.5 to 3, particularly preferably 2.7.
[0175] 33. Any one of embodiments 1-32, wherein a polyisocyanate is used in component A at a 4:1 NCO equivalent ratio relative to the OH groups in the polyol to ensure that the prepolymer is NCO-terminated.
[0176] 34. The component of the NCO-terminated prepolymer is 1. Polyols: based on the total weight of component A, 2 to 10% by weight, more preferably 3 to 6% by weight, more particularly preferably 4 to 5% by weight of poly(propylene oxide) diols having an equivalent weight of 200 to 250 g / eq, and 6 to 15% by weight, more preferably 8 to 12% by weight, particularly preferably 9 to 10% by weight of poly(propylene oxide)-based diols having an average equivalent weight of 475 to 550 g / eq, and Isocyanates: 25 to 35% by weight, more preferably 28 to 32% by weight, particularly preferably 30 to 31% by weight, of MDI having a functionality of 2 to 2.3, particularly preferably 2.2, based on the total weight of component A, and 0.25 to 1% by weight, more preferably 0.3 to 0.8% by weight, particularly preferably 0.5 to 0.7% by weight, of MDI having a functionality of 2.5 to 3, particularly preferably 2.7, based on the total weight of component A, or 2. Polyol: 4-5% by weight of poly(propylene oxide) diol having an equivalent weight of 200-250 g / eq, and 9-10% by weight of poly(propylene oxide)-based diol having an average equivalent weight of 475-550 g / eq, and Isocyanate: 30 to 31 wt.-% of MDI having a functionality of 2 to 2.3, particularly preferably 2.2, based on the total weight of component A, and 0.5 to 0.7 wt.-% of MDI having a functionality of 2.5 to 3, particularly preferably 2.7, based on the total weight of component A, according to any one of the preceding embodiments.
[0177] 35. Any one of embodiments 1-34, wherein component A comprises an adhesion promoter.
[0178] 36. Any one of embodiments 1-35, wherein component A comprises an adhesion promoter that is a reactive silane.
[0179] 37. Any one of the preceding embodiments, wherein component A comprises an adhesion promoter that is a silane containing a mercapto group, a primary or secondary amine group, or a hydrolyzable silylalkoxy group covalently bonded to an epoxy group.
[0180] 38. Any one of the preceding embodiments, wherein component A comprises an epoxy silane.
[0181] 39. Embodiment 38, wherein the epoxy silane is selected from glycidyloxyalkyl(trialkoxy)silanes and glycidyloxyalkyl(methyl-dialkoxy)silanes.
[0182] 40. Any one of embodiments 1-39, wherein component A comprises (3-glycidyloxypropyl)trimethoxysilane.
[0183] 41. Any one of embodiments 1 to 40, wherein component A comprises 0.1 to 1 wt. %, more preferably 0.25 to 0.75 wt. %, and particularly preferably 0.4 to 0.6 wt. % of the reactive silane, based on the total weight of component A.
[0184] 42. Any one of embodiments 1 to 41, wherein component A comprises 0.1 to 1 wt. %, more preferably 0.25 to 0.75 wt. %, and particularly preferably 0.4 to 0.6 wt. % of glycidyloxypropyl)trimethoxysilane, based on the total weight of component A.
[0185] 43. Any one of the preceding embodiments, wherein at least one polyol used to make the OH-terminated prepolymer of component B is a polyether polyol.
[0186] 44. Any one of embodiments 1 to 43, wherein at least one polyol used to make the OH-terminated prepolymer is selected from polyols having a functionality of 2 or more, more preferably 3 or more.
[0187] 45. Any one of embodiments 1 to 44, wherein the polyol used to prepare the OH-terminated prepolymer is selected from poly(C2-C4-alkylene oxide) polyols, in particular poly(ethylene oxide) polyols, poly(propylene oxide) polyols, poly(tetramethylene oxide) polyols, and mixtures thereof.
[0188] 46. Any one of embodiments 1-45, wherein the polyol used to make the OH-terminated prepolymer is a poly(propylene oxide) polyol.
[0189] 47. Any one of embodiments 1-46, wherein the polyol used to make the OH-terminated prepolymer is selected from poly(propylene oxide) polyols having a functionality of 3 or greater.
[0190] 48. Any one of the preceding embodiments, wherein at least one polyol used to make the OH-terminated prepolymer has an average equivalent weight of 800 to 1,800 g / eq, more preferably 1,200 to 1,700 g / eq.
[0191] 49. Any one of embodiments 1 to 48, wherein at least one polyol used to make the OH-terminated prepolymer is a triol having an average equivalent weight of 800 to 1,800 g / eq, more preferably 1,200 to 1,700 g / eq.
[0192] 50. Any one of embodiments 1-49, wherein at least one polyol used to make the OH-terminated prepolymer is a poly(propylene oxide)-based triol having an average equivalent weight of 800 to 1,800 g / eq, more preferably 1,200 to 1,700 g / eq.
[0193] 51. Any one of embodiments 1-50, wherein at least one polyol used to make the OH-terminated prepolymer is a poly(propylene oxide)-based triol having an average equivalent weight of 1,500-1,700 g / eq.
[0194] 52. Any one of the embodiments 1 to 51, wherein the at least one polyol used to prepare the OH-terminated prepolymer is used in an amount of 25 to 40% by weight, more preferably 27 to 35% by weight, particularly preferably 32 to 34% by weight, based on the total weight of component B.
[0195] 53. Any one of embodiments 1 to 52, wherein component B comprises 25 to 40 wt. %, more preferably 27 to 35 wt. %, and particularly preferably 32 to 34 wt. %, based on the total weight of component B, of a poly(propylene oxide)-based triol having an average equivalent weight of 1,500 to 1,700 g / eq.
[0196] 54. Any one of embodiments 1-53, wherein at least one polyisocyanate used to make the OH-terminated prepolymer is aromatic.
[0197] 55. Any one of the preceding embodiments, wherein the at least one polyisocyanate used to prepare the OH-terminated prepolymer is selected from toluene diisocyanate (TDI), hexamethylene diisocyanate (HDI), naphthalene diisocyanate (NDI), methylene bis-cyclohexyl isocyanate (HMDI) (hydrogenated MDI), MDI (especially 4,4'- and 4,2-MDI) and isophorone diisocyanate (IPDI), and mixtures thereof.
[0198] 56. Any one of embodiments 1-55, wherein at least one polyisocyanate used to make the OH-terminated prepolymer is MDI.
[0199] 57. Any one of the preceding embodiments, wherein at least one polyisocyanate used to prepare the OH-terminated prepolymer is MDI having a functionality of 2 or more, in particular a functionality of 2 to 3, particularly preferably a functionality of 2 to 2.3.
[0200] 58. Any one of embodiments 1 to 57, wherein the total polyisocyanate content of component B is 0.25 to 2.5% by weight, more preferably 0.5 to 2% by weight, and particularly preferably 1.2 to 1.6% by weight, based on the total weight of component B.
[0201] 59. Any one of embodiments 1 to 58, wherein component B comprises 0.25 to 2.5 wt.-%, more preferably 0.5 to 2 wt.-%, particularly preferably 1.2 to 1.6 wt.-%, of MDI having a functionality of 2 to 2.3, particularly preferably 2.2, based on the total weight of component B.
[0202] 60. Any one of embodiments 1-59, wherein a polyisocyanate is used in component B at a 1:10 NCO equivalent ratio relative to the OH groups in the polyol to ensure that the prepolymer is OH-terminated.
[0203] 61. An OH-terminated prepolymer having the following components: 1. Polyol: 25 to 40% by weight, more preferably 27 to 35% by weight, particularly preferably 32 to 34% by weight, of a poly(propylene oxide) triol having an equivalent weight of 1,500 to 1,700 g / eq, based on the total weight of component B; and Isocyanate: 0.25 to 2.5% by weight, more preferably 0.5 to 2% by weight, particularly preferably 1.2 to 1.6% by weight, of MDI having a functionality of 2 to 2.3, particularly preferably 2.2, based on the total weight of component B, or 2. Polyol: 32-34 wt. % of a poly(propylene oxide) triol having an equivalent weight of 1,500-1,700 g / eq, based on the total weight of component B; and Isocyanate: any one of the embodiments 1 to 60, which is made from 1.2 to 1.6 wt.-%, based on the total weight of component B, of MDI having a functionality of 2 to 2.3, particularly preferably 2.2.
[0204] 62. Any one of the preceding embodiments, wherein the catalyst is selected from a tertiary amine catalyst, an organometallic catalyst, and mixtures thereof.
[0205] 63. The catalyst is N-methylmorpholine, N-methylimidazole, triethylenediamine, bis-(2-dimethylaminoethyl)-ether, 1,4-diazabicyclo[2.2.2]octane (DABCO), dimethylcyclohexylamine, dimethylethanolamine, 2,2-dimorpholinyl diethyl ether (DMDEE), N,N,N-dimethylaminopropyl hexahydrotriazine, dimethyltetrahydropyrimidine, tetramethylethylenediamine, dimethylcyclohexylamine, 2,2-N,N-benzyldimethylamine, dimethylethanolamine 63. Any one of the preceding embodiments, wherein the trimethylaminoethyl amine is selected from N,N,N',N'-tetramethyl-1,6-hexanediamine, N,N',N'-trimethylaminoethylpiperazine, 1,1'-[[3-(dimethylamino)propyl]imino]bispropan-2-ol, 1,3,5-tris[3-(dimethylamino)propyl]hexahydro-1,3,5-triazine, N-N-dimethyldipropylenetriamine, N,N,N'-trimethylaminoethylethanolamine, and mixtures thereof.
[0206] 64. Any one of the preceding embodiments, wherein the catalyst is selected from organotin catalysts.
[0207] 65. Any one of the preceding embodiments, wherein the catalyst is selected from dibutyltin dilaurate, dimethyltin dineodecanoate, dimethyltin mercaptide, dimethyltin carboxylate, dimethyltin dioleate, dimethyltin dithioglycolate, dibutyltin mercaptide, dibutyltin bis(2-ethylhexylthioglycolate), dibutyltin sulfide, dioctyltin dithioglycolate, dioctyltin mercaptide, dioctyltin dioctoate, dioctyltin dineodecanoate, dioctyltin dilaurate, and mixtures thereof.
[0208] 66. Any one of the preceding embodiments, wherein the catalyst is selected from dioctyltin mercaptide, dimethyltin dithioglycolate, and mixtures thereof.
[0209] 67. Any one of the embodiments 1 to 66, wherein the catalyst is used in an amount of 0.02 to 0.12 wt. %, more preferably 0.03 to 0.1 wt. %, based on the total weight of component B.
[0210] 68. Any one of embodiments 1 to 67, wherein the catalyst is dioctyltin mercaptide, used at 0.03 to 0.07 wt.%, based on the total weight of component B, and dimethyltin dithioglycolate, used at 0.001 to 0.003 wt.%, based on the total weight of component B.
[0211] 69. Any one of embodiments 1-68, wherein component B comprises an adhesion promoter.
[0212] 70. Any one of embodiments 1-69, wherein component B comprises a reactive silane.
[0213] 71. Embodiment 70, wherein the reactive silane is a hydrolyzable silylalkoxy group covalently bonded to a mercapto group, a primary or secondary amine group, or an epoxy group.
[0214] 72. Any one of embodiments 1-71, wherein component B comprises an epoxy silane.
[0215] 73. Embodiment 72, wherein the epoxy silane is selected from glycidyloxyalkyl(trialkoxy)silanes and glycidyloxyalkyl(methyl-dialkoxy)silanes.
[0216] 74. Embodiment 72, wherein the epoxy silane is selected from tris(diethylene glycol methyl ether)silyl propylene glycidyl ether, (3-glycidyloxypropyl)trimethoxysilane, (3-glycidyloxypropyl)triethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 2-(3,4-epoxycyclohexyl)-ethyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)-ethyltriethoxysilane, and mixtures thereof.
[0217] 75. Any one of embodiments 1-74, wherein component B comprises (3-glycidyloxypropyl)trimethoxysilane.
[0218] 76. Any one of embodiments 1 to 75, wherein component B comprises 0.1 to 1 wt. %, more preferably 0.25 to 0.75 wt. %, and particularly preferably 0.4 to 0.6 wt. % of the reactive silane, based on the total weight of component B.
[0219] 77. Any one of embodiments 1 to 76, wherein component B comprises, based on the total weight of component B, 0.1 to 1 wt. %, more preferably 0.25 to 0.75 wt. %, and particularly preferably 0.4 to 0.6 wt. % of glycidyloxypropyl)trimethoxysilane.
[0220] 78. Any one of embodiments 1-77, wherein the aluminum trihydroxide has a bimodal particle size distribution.
[0221] 79. Aluminum trihydroxide is D 90~120μm 90 , more preferably 95 to 105 μm D 90 and aluminum trihydroxide having the formula D of 15 to 25 μm, preferably 18 to 21 μm 90 Any one of the preceding embodiments, comprising or consisting of a mixture of aluminum trihydroxide having the formula:
[0222] 80. Aluminum trihydroxide has the following particle size distribution: Any one of embodiments 1-79, wherein 1-20% by weight have less than 1 μm, 5-30% by weight have 1-10 μm, 3-30% by weight have 10-20 μm, more than 10% by weight have 20-50 μm, and more than 35% by weight have 50-100 μm.
[0223] 81. Aluminum trihydroxide has the following particle size distribution: Any one of embodiments 1-80, wherein 1-10% by weight has a particle size less than 1 μm, 5-20% by weight has a particle size of 1-10 μm, 3-20% by weight has a particle size of 10-20 μm, 10-40% by weight has a particle size of 20-50 μm, and 35-70% by weight has a particle size of 50-100 μm.
[0224] 82. Aluminum trihydroxide has the following particle size distribution: Any one of the embodiments 1-81, wherein 1-5 wt% has a particle size less than 1 μm, 5-15 wt% has a particle size of 1-10 μm, 5-15 wt% has a particle size of 10-20 μm, 15-35 wt% has a particle size of 20-50 μm, and 40-60 wt% has a particle size of 50-100 μm.
[0225] 83. Aluminum trihydroxide is D 95~105μm 90 and aluminum trihydroxide having the formula D 18~21μm 90 Any one of the preceding embodiments, comprising or consisting of a mixture of aluminum trihydroxide having the formula:
[0226] 84. Aluminum trihydroxide is D 90~120μm 90 , more preferably 95 to 105 μm D 90 , and D of 45 to 55 μm 50 , more preferably 48 to 52 μm D 50 and aluminum trihydroxide having the formula D of 15 to 25 μm, preferably 18 to 21 μm 90 , and D of 5 to 10 μm 50 , more preferably 6 to 9 μm D 50 Any one of the preceding embodiments, comprising or consisting of a mixture of aluminum trihydroxide having the formula:
[0227] 85. Aluminum trihydroxide is D 90~120μm 90 , more preferably 95 to 105 μm D 90 , 45-55μm D 50 , more preferably 48 to 52 μm D 50, and 8 to 12 μm, more preferably 9 to 11 μm D 10 and aluminum trihydroxide having the formula D of 15 to 25 μm, preferably 18 to 21 μm 90 , and D of 5 to 10 μm 50 , more preferably 6 to 9 μm D 50 Any one of the preceding embodiments, comprising or consisting of a mixture of aluminum trihydroxide having the formula:
[0228] 86. Aluminum trihydroxide is, based on the total amount of aluminum trihydroxide, D 90~120μm 90 , more preferably 95 to 105 μm D 90 80 to 95% by weight of aluminum trihydroxide having the formula: D of 15 to 25 μm, preferably 18 to 21 μm 90 5 to 20% by weight of aluminum trihydroxide having Any one of the preceding embodiments, comprising or consisting of a mixture of:
[0229] 87. Aluminum trihydroxide is, based on the total amount of aluminum trihydroxide, D 95~105μm 90 80 to 95% by weight of aluminum trihydroxide having the formula: D 18~21μm 90 5 to 20% by weight of aluminum trihydroxide having Any one of the preceding embodiments, comprising or consisting of a mixture of:
[0230] 88. Aluminum trihydroxide is, based on the total amount of aluminum trihydroxide, D 90~120μm 90 , more preferably 95 to 105 μm D 90 , and D of 45 to 55 μm 50 , more preferably 48 to 52 μm D 50 80 to 95% by weight of aluminum trihydroxide having the formula: D of 15 to 25 μm, preferably 18 to 21 μm 90, and D of 5 to 10 μm 50 , more preferably 6 to 9 μm D 50 5 to 20% by weight of aluminum trihydroxide having Any one of the preceding embodiments, comprising or consisting of a mixture of:
[0231] 89. Aluminum trihydroxide is, based on the total amount of aluminum trihydroxide, D 90~120μm 90 , more preferably 95 to 105 μm D 90 , 45-55μm D 50 , more preferably 48 to 52 μm D 50 , and 8 to 12 μm, more preferably 9 to 11 μm D 10 80 to 95% by weight of aluminum trihydroxide having the formula: D of 15 to 25 μm, preferably 18 to 21 μm 90 , and D of 5 to 10 μm 50 , more preferably 6 to 9 μm D 50 5 to 20% by weight of aluminum trihydroxide having Any one of the preceding embodiments, comprising or consisting of a mixture of:
[0232] 90. Any one of embodiments 1-89, wherein ATH is present in component A, component B, or both.
[0233] 91. Any one of embodiments 1-90, wherein both component A and component B comprise ATH.
[0234] 92. Any one of embodiments 1-91, wherein component A comprises 40-60% by weight ATH, more preferably 45-55% by weight ATH, based on the total weight of component A.
[0235] 93. Any one of embodiments 1-92, wherein component B comprises 40-60% by weight ATH, more preferably 45-55% by weight ATH, based on the total weight of component B.
[0236] 94. Any one of embodiments 1-93, wherein component A comprises 40-60% ATH by weight, more preferably 45-55% ATH by weight, based on the total weight of component A, and component B comprises 40-60% ATH by weight, more preferably 45-55% ATH by weight, based on the total weight of component B.
[0237] 95. Any one of the preceding embodiments, wherein component A and / or component B comprises graphite having an aspect ratio of 0.8 to 1.2, more preferably 0.9 to 1.1.
[0238] 96. The spherical graphite has a D of 5 to 50 μm, more preferably 10 to 20 μm, and particularly preferably 15 to 16.2 μm. 50 Any one of embodiments 1 to 95, comprising:
[0239] 97. The spherical graphite has a D of 30 to 60 μm, more preferably 35 to 50 μm, and particularly preferably 40 to 48 μm. 90 Any one of embodiments 1 to 96, comprising:
[0240] 98. The spherical graphite has a D of 5 to 50 μm, more preferably 10 to 20 μm, and particularly preferably 15 to 16.2 μm. 50 and D of 30 to 60 μm, more preferably 35 to 50 μm, particularly preferably 40 to 48 μm. 90 Any one of embodiments 1 to 97, comprising:
[0241] 99. Spherical graphite, 1-20m 2 / g, more preferably 5 to 15m 2 / g, particularly preferably 9m 2 Any one of the preceding embodiments having a BET surface area of 1.0 to 1.0 g / g.
[0242] 100. The spherical graphite has a D of 5 to 50 μm, more preferably 10 to 20 μm, and particularly preferably 15 to 16.2 μm. 50 , and 1 to 20 m 2 / g, more preferably 5 to 15m 2 / g, particularly preferably 9m2 Any one of the preceding embodiments having a BET surface area of 1.0 to 1.0 g / g.
[0243] 101. The spherical graphite has a D of 30 to 60 μm, more preferably 35 to 50 μm, and particularly preferably 40 to 48 μm. 90 , and 1 to 20 m 2 / g, more preferably 5 to 15m 2 / g, particularly preferably 9m 2 Any one of the preceding embodiments, having a BET surface area of 100 to 200 nm / g.
[0244] 102. The spherical graphite has a D of 5 to 50 μm, more preferably 10 to 20 μm, and particularly preferably 15 to 16.2 μm. 50 and D of 30 to 60 μm, more preferably 35 to 50 μm, particularly preferably 40 to 48 μm. 90 , and 1 to 20 m 2 / g, more preferably 5 to 15m 2 / g, particularly preferably 9m 2 Any one of the preceding embodiments, having a BET surface area of 100 / g.
[0245] 103. Any one of embodiments 1-102, wherein spherical graphite is present in component A, component B, or both.
[0246] 104. Any one of embodiments 1-103, wherein both component A and component B comprise spherical graphite.
[0247] 105. Any one of the preceding embodiments, wherein component A comprises 2 to 15 wt. %, more preferably 4 to 8 wt. %, of spherical graphite, based on the total weight of component A.
[0248] 106. Any one of the preceding embodiments, wherein component B comprises 5 to 20% by weight, more preferably 8 to 12% by weight, of spherical graphite, based on the total weight of component B.
[0249] 107. Any one of embodiments 1 to 106, wherein component A contains 2 to 15% by weight, more preferably 4 to 8% by weight, of spherical graphite, based on the total weight of component A, and component B contains 5 to 20% by weight, more preferably 8 to 12% by weight, of spherical graphite, based on the total weight of component B.
[0250] Any one of the preceding embodiments, wherein the graphite having an aspect ratio greater than 108.2 has an aspect ratio greater than 3.
[0251] Any one of the preceding embodiments, wherein the graphite having an aspect ratio greater than 109.2 has an aspect ratio greater than 4.
[0252] Any one of embodiments 1-109, wherein the graphite having an aspect ratio greater than 110.2 is selected from graphite particles, graphene platelets, and mixtures thereof.
[0253] Graphite having an aspect ratio of greater than 111.2 has a D of 80 to 110 μm, more preferably 85 to 95 μm. 90 Any one of the preceding embodiments, wherein the graphite particles have the formula:
[0254] Any one of embodiments 1-111, wherein the graphite having an aspect ratio of more than 112.2 is a graphene nanoplatelet having a thickness of 10-30 nm, preferably 16-20 nm, and an average particle size of 10-35 μm, more preferably 15-30 μm, particularly preferably 24-26 μm.
[0255] Any one of the preceding embodiments, wherein graphite having an aspect ratio greater than 113.2 is present in component A, component B, or both.
[0256] 114. Any one of embodiments 1-113, wherein both component A and component B comprise graphite having an aspect ratio greater than 2.
[0257] 115. Any one of embodiments 1 to 114, wherein component A comprises 0.5 to 2.5 wt. %, more preferably 0.75 to 2 wt. %, and particularly preferably 0.0 to 1.3 wt. %, of graphite having an aspect ratio greater than 2, based on the total weight of component A.
[0258] 116. Any one of embodiments 1 to 115, wherein component B comprises 0.5 to 2.5 wt. %, more preferably 0.75 to 2 wt. %, and particularly preferably 0.0 to 1.3 wt. %, of graphite having an aspect ratio greater than 2, based on the total weight of component B.
[0259] 117. Any one of embodiments 1 to 116, wherein component A comprises 0.5 to 2.5 wt. %, more preferably 0.75 to 2 wt. %, and particularly preferably 0.0 to 1.3 wt. %, of graphite having an aspect ratio greater than 2, based on the total weight of component A, and component B comprises 0.5 to 2.5 wt. %, more preferably 0.75 to 2 wt. %, and particularly preferably 0.0 to 1.3 wt. %, of graphite having an aspect ratio greater than 2, based on the total weight of component B.
[0260] 118. Any one of the preceding embodiments, wherein component A and / or component B comprises the following combination of fillers: 1. D 90~120μm 90 , more preferably 95 to 105 μm D 90 and aluminum trihydroxide having the formula D of 15 to 25 μm, preferably 18 to 21 μm 90 ATH comprising or consisting of a mixture with aluminum trihydroxide having Spherical graphite, and Graphite with an aspect ratio greater than 2
[0261] 2. D 95~105μm 90 and aluminum trihydroxide having the formula D 18~21μm 90ATH comprising or consisting of a mixture with aluminum trihydroxide having Spherical graphite, and Graphite with an aspect ratio greater than 2
[0262] 3. D 90~120μm 90 , more preferably 95 to 105 μm D 90 , and D of 45 to 55 μm 50 , more preferably 48 to 52 μm D 50 and aluminum trihydroxide having the formula D of 15 to 25 μm, preferably 18 to 21 μm 90 , and D of 5 to 10 μm 50 , more preferably 6 to 9 μm D 50 ATH comprising or consisting of a mixture with aluminum trihydroxide having Spherical graphite, and Graphite with an aspect ratio greater than 2
[0263] 4. D 90~120μm 90 , more preferably 95 to 105 μm D 90 , 45-55μm D 50 , more preferably 48 to 52 μm D 50 , and 8 to 12 μm, more preferably 9 to 11 μm D 10 and aluminum trihydroxide having the formula D of 15 to 25 μm, preferably 18 to 21 μm 90 , and D of 5 to 10 μm 50 , more preferably 6 to 9 μm D 50 ATH comprising or consisting of a mixture with aluminum trihydroxide having Spherical graphite, and Graphite with an aspect ratio greater than 2
[0264] 5. Based on the total amount of aluminum trihydroxide, D 90~120μm 90, more preferably 95 to 105 μm D 90 80 to 95% by weight of aluminum trihydroxide having the formula: D of 15 to 25 μm, preferably 18 to 21 μm 90 ATH comprising or consisting of a mixture of 5 to 20% by weight of aluminum trihydroxide having the formula: Spherical graphite, and Graphite with an aspect ratio greater than 2
[0265] 6. Based on the total amount of aluminum trihydroxide, D 95~105μm 90 80 to 95% by weight of aluminum trihydroxide having the formula: D 18~21μm 90 ATH comprising or consisting of a mixture of 5 to 20% by weight of aluminum trihydroxide having the formula: Spherical graphite, and Graphite with an aspect ratio greater than 2
[0266] 7. Based on the total amount of aluminum trihydroxide, D 90~120μm 90 , more preferably 95 to 105 μm D 90 , and D of 45 to 55 μm 50 , more preferably 48 to 52 μm D 50 80 to 95% by weight of aluminum trihydroxide having the formula: D of 15 to 25 μm, preferably 18 to 21 μm 90 , and D of 5 to 10 μm 50 , more preferably 6 to 9 μm D 50 ATH comprising or consisting of a mixture of 5 to 20% by weight of aluminum trihydroxide having the formula: Spherical graphite, and Graphite with an aspect ratio greater than 2
[0267] 8. Based on the total amount of aluminum trihydroxide, D 90~120μm 90, more preferably 95 to 105 μm D 90 , 45-55μm D 50 , more preferably 48 to 52 μm D 50 , and 8 to 12 μm, more preferably 9 to 11 μm D 10 80 to 95% by weight of aluminum trihydroxide having the formula: D of 15 to 25 μm, preferably 18 to 21 μm 90 , and D of 5 to 10 μm 50 , more preferably 6 to 9 μm D 50 ATH comprising or consisting of a mixture of 5 to 20% by weight of aluminum trihydroxide having the formula: Spherical graphite, and Graphite with an aspect ratio greater than 2
[0268] 9. D 90~120μm 90 , more preferably 95 to 105 μm D 90 and aluminum trihydroxide having the formula D of 15 to 25 μm, preferably 18 to 21 μm 90 ATH comprising or consisting of a mixture with aluminum trihydroxide having D of 5 to 50 μm, more preferably 10 to 20 μm, particularly preferably 15 to 16.2 μm 50 Spherical graphite having the formula: Graphite with an aspect ratio greater than 2
[0269] 10. D 95~105μm 90 and aluminum trihydroxide having the formula D 18~21μm 90 ATH comprising or consisting of a mixture with aluminum trihydroxide having D of 5 to 50 μm, more preferably 10 to 20 μm, particularly preferably 15 to 16.2 μm 50 Spherical graphite having the formula: Graphite with an aspect ratio greater than 2
[0270] 11. D 90~120μm 90 , more preferably 95 to 105 μm D 90 , and D of 45 to 55 μm 50 , more preferably 48 to 52 μm D 50 and aluminum trihydroxide having the formula D of 15 to 25 μm, preferably 18 to 21 μm 90 , and D of 5 to 10 μm 50 , more preferably 6 to 9 μm D 50 ATH comprising or consisting of a mixture with aluminum trihydroxide having D of 5 to 50 μm, more preferably 10 to 20 μm, particularly preferably 15 to 16.2 μm 50 Spherical graphite having the formula: Graphite with an aspect ratio greater than 2
[0271] 12. D 90~120μm 90 , more preferably 95 to 105 μm D 90 , 45-55μm D 50 , more preferably 48 to 52 μm D 50 , and 8 to 12 μm, more preferably 9 to 11 μm D 10 and aluminum trihydroxide having the formula D of 15 to 25 μm, preferably 18 to 21 μm 90 , and D of 5 to 10 μm 50 , more preferably 6 to 9 μm D 50 ATH comprising or consisting of a mixture with aluminum trihydroxide having D of 5 to 50 μm, more preferably 10 to 20 μm, particularly preferably 15 to 16.2 μm 50 Spherical graphite having the formula: Graphite with an aspect ratio greater than 2
[0272] 13. Based on the total amount of aluminum trihydroxide, D 90~120μm 90 , more preferably 95 to 105 μm D 9080 to 95% by weight of aluminum trihydroxide having the formula: D of 15 to 25 μm, preferably 18 to 21 μm 90 ATH comprising or consisting of a mixture of 5 to 20% by weight of aluminum trihydroxide having the formula: D of 5 to 50 μm, more preferably 10 to 20 μm, particularly preferably 15 to 16.2 μm 50 Spherical graphite having the formula: Graphite with an aspect ratio greater than 2
[0273] 14. Based on the total amount of aluminum trihydroxide, D 95~105μm 90 80 to 95% by weight of aluminum trihydroxide having the formula: D 18~21μm 90 ATH comprising or consisting of a mixture of 5 to 20% by weight of aluminum trihydroxide having the formula: D of 5 to 50 μm, more preferably 10 to 20 μm, particularly preferably 15 to 16.2 μm 50 Spherical graphite having the formula: Graphite with an aspect ratio greater than 2
[0274] 15. Based on the total amount of aluminum trihydroxide, D 90~120μm 90 , more preferably 95 to 105 μm D 90 , and D of 45 to 55 μm 50 , more preferably 48 to 52 μm D 50 80 to 95% by weight of aluminum trihydroxide having the formula: D of 15 to 25 μm, preferably 18 to 21 μm 90 , and D of 5 to 10 μm 50 , more preferably 6 to 9 μm D 50 ATH comprising or consisting of a mixture of 5 to 20% by weight of aluminum trihydroxide having the formula: D of 5 to 50 μm, more preferably 10 to 20 μm, particularly preferably 15 to 16.2 μm 50 Spherical graphite having the formula: Graphite with an aspect ratio greater than 2
[0275] 16. Based on the total amount of aluminum trihydroxide, D 90~120μm 90 , more preferably 95 to 105 μm D 90 , 45-55μm D 50 , more preferably 48 to 52 μm D 50 , and 8 to 12 μm, more preferably 9 to 11 μm D 10 80 to 95% by weight of aluminum trihydroxide having the formula: D of 15 to 25 μm, preferably 18 to 21 μm 90 , and D of 5 to 10 μm 50 , more preferably 6 to 9 μm D 50 ATH comprising or consisting of a mixture of 5 to 20% by weight of aluminum trihydroxide having the formula: D of 5 to 50 μm, more preferably 10 to 20 μm, particularly preferably 15 to 16.2 μm 50 Spherical graphite having the formula: Graphite with an aspect ratio greater than 2
[0276] 17. ATH having a bimodal particle size distribution, and Spherical graphite, and Graphite with an aspect ratio greater than 2
[0277] 18. ATH having a bimodal particle size distribution, and D of 5 to 50 μm, more preferably 10 to 20 μm, particularly preferably 15 to 16.2 μm 50 Spherical graphite having the formula: Graphite with an aspect ratio greater than 2
[0278] 19. ATH having a particle size distribution of 1-20% by volume less than 1 μm, 10-30% by volume 1-10 μm, 5-30% by volume 10-20 μm, more than 10% by volume 20-50 μm, and more than 20% by volume 50-100 μm; and Spherical graphite, and Graphite with an aspect ratio greater than 2
[0279] 20. ATH having a particle size distribution of 1-20% by volume less than 1 μm, 10-30% by volume 1-10 μm, 5-30% by volume 10-20 μm, more than 10% by volume 20-50 μm, and more than 20% by volume 50-100 μm; and D of 5 to 50 μm, more preferably 10 to 20 μm, particularly preferably 15 to 16.2 μm 50 Spherical graphite having the formula: Graphite with an aspect ratio greater than 2
[0280] 119. Any one of the preceding embodiments, wherein the combination of fillers is present in component A, component B, or both, preferably both component A and component B contain the combination of fillers.
[0281] 120. Any one of embodiments 1-119, wherein component A comprises 45-75% total filler by weight, more preferably 50-60% total filler by weight, based on the total weight of component A.
[0282] 121. Any one of embodiments 1-120, wherein component B comprises 45-75% total filler by weight, more preferably 50-60% total filler by weight, based on the total weight of component B.
[0283] 122. Any one of embodiments 1-121, wherein component A comprises 45-75% total filler by weight, more preferably 50-60% total filler by weight, based on the total weight of component A, and component B comprises 45-75% total filler by weight, more preferably 50-60% total filler by weight, based on the total weight of component B.
[0284] 123. Any one of embodiments 1-122, wherein component A and component B are mixed in a volume ratio A:B of 0.8 to 1.2, more preferably 1:1.
[0285] 124. Any one of embodiments 1-123, wherein component B comprises a diol or triol having a molecular weight of less than 200 Da.
[0286] 125. Any one of embodiments 1-124, wherein component B comprises 1,4-butanediol. EXAMPLES
[0287] [Table 1]
[0288] [Table 2]
[0289] Adhesive Formulation Component A (isocyanate) and Component B (polyol) were prepared in a 4-5 L planetary mixer laboratory scale mixer. The components listed in Table 2 were used.
[0290] To prepare Component B (polyol), an OH-terminated prepolymer was first prepared by mixing the polyol components of Component B listed in Table 2. The isocyanate component was then added and the mixture was mixed in a planetary mixer under vacuum and at a temperature of 35° C. The filler component was then added and mixed for 45 minutes under a vacuum of 80 mbar. The vacuum was released under nitrogen and Component B was filled into cartridges until use.
[0291] To prepare Component A (isocyanate), an isocyanate-terminated prepolymer was first prepared by mixing the polyol components (diols and / or triols) of Component A. The isocyanate component was then added at room temperature with stirring. The filler component was then added and the mixture was heated to 70° C. and stirred for 60 minutes under a vacuum of 80 mbar. The material was actively cooled to a temperature below 30° C. The vacuum was released under nitrogen and Component A was filled and stored in cartridges until use.
[0292] Components A and B were stored separately until use. Immediately prior to use, the components were mixed in a 1:1 volume ratio. The resulting adhesive was cured at 23° C. for 7 days and the properties were measured.
[0293] Test Method Thermal Conductivity Thermal conductivity: Thermal conductivity was measured according to ASTM5470. A thermal interface material tester from ZFW Stuttgart was used for the test. The top contact was heated to about 40°C and the bottom contact was heated to about 10°C, resulting in a sample temperature gradient of about 25°C. The test was performed on the cured material (7 days, 23°C, 50% RH), thickness 2 mm. To ensure better contact between the material to be tested and the top and bottom heated contacts, a thermally conductive oil, KRYO 30 from Lauda, was added to the surface of the cured material and pressure up to 10 bar was applied between the thermal contacts. The absolute thermal conductivity λeff (W / mK) is recorded.
[0294] Elongation at break The elongation at break was measured according to ISO EN 572-2.
[0295] Lap Shear Strength Lap shear strength was measured according to DIN EN 1465. The specimens were e-coated steel with dimensions 100 x 25 x 1.6 and a bond area of 15 mm and a bond thickness of 1 mm. The adhesive was cured at 23°C for 7 days. Lap shear strength was also evaluated after exposure at 70°C and 100% relative humidity (RH) for 7 days.
[0296] Dielectric Strength The dielectric strength was measured according to IEC 60243 / ASTM D 149-97A using adhesive samples obtained by mixing component A and component B in a 1:1 volume ratio and curing the adhesive at 23°C and 50% relative humidity for 7 days.
[0297] Volume resistivity The volume resistivity was determined according to DIN IEC 60093 on samples of an adhesive obtained by mixing component A and component B in a 1:1 volume ratio and curing the adhesive for 7 days at 23° C. and 50% relative humidity.
[0298]
Table 3
[0299]
Table 4
Claims
1. A two-part thermally conductive polyurethane adhesive comprising: A. a first component (isocyanate) comprising an NCO-terminated prepolymer made by reacting at least one polyol with at least one polyisocyanate; B. A second component (polyol) comprising an OH-terminated prepolymer made by reacting at least one polyol with at least one polyisocyanate and a catalyst capable of catalyzing the reaction of isocyanate groups with OH groups; Component A and / or Component B may comprise the following fillers: aluminium trihydroxide having a polymodal (preferably bimodal) particle size distribution; Graphite having a spherical particle shape, and Graphite having an aspect ratio of greater than 2; As a result, a two-part thermally conductive polyurethane adhesive, wherein when component A and component B are mixed together to form an adhesive mixture, said adhesive mixture comprises greater than 40% by weight aluminum trihydroxide and greater than 8% by weight graphite.
2. The adhesive of claim 1 , wherein the at least one polyol used to make the NCO-terminated prepolymer is a polyether polyol.
3. The adhesive of claim 1 , wherein the at least one polyol used to make the NCO-terminated prepolymer is selected from polyols having a functionality of 2 or greater.
4. The adhesive of claim 1 , wherein the at least one polyol used to make the NCO-terminated prepolymer has a functionality of two.
5. The polyol used to make the NCO-terminated prepolymer is poly(C 2 ~C 4 2. The adhesive according to claim 1, wherein the poly(alkylene oxide) polyol is selected from poly(ethylene oxide) polyols, poly(propylene oxide) polyols, poly(tetramethylene oxide) polyols, and mixtures thereof.
6. The adhesive of claim 1 , wherein the polyol used to make the NCO-terminated prepolymer is a poly(propylene oxide) polyol.
7. The adhesive of claim 1, wherein the polyol used to make the NCO-terminated prepolymer is selected from poly(propylene oxide) polyols having a functionality of 2-3.
8. The adhesive of claim 1, wherein the at least one polyol used to make the NCO-terminated prepolymer has a molecular weight of 400 to 2,500 Da.
9. The adhesive of claim 1, wherein the at least one polyol used to make the NCO-terminated prepolymer preferably has an average equivalent weight of 200 to 1,250 g / eq.
10. The adhesive of claim 1 , wherein the at least one polyol used to make the NCO-terminated prepolymer is a mixture of polyols.
11. 2. The adhesive of claim 1, wherein the at least one polyol used to make the NCO-terminated prepolymer is a mixture of polyols including a polyol having an average equivalent weight of 200 to 250 g / eq and a polyol having an average equivalent weight of 475 to 550 g / eq.
12. 2. The adhesive of claim 1, wherein the at least one polyol used to make the NCO-terminated prepolymer is a mixture of a poly(propylene oxide)-based polyol having an average equivalent weight of 200 to 250 g / eq and a poly(propylene oxide)-based polyol having an average equivalent weight of 475 to 550 g / eq.
13. 2. The adhesive of claim 1, wherein the at least one polyol used to make the NCO-terminated prepolymer is a mixture of a poly(propylene oxide)-based diol having an average equivalent weight of 200-250 g / eq and a poly(propylene oxide)-based diol having an average equivalent weight of 475-550 g / eq.
14. 2. The adhesive of claim 1, wherein the at least one polyol used to make the NCO-terminated prepolymer comprises a poly(propylene oxide)-based polyol (P1) having an average equivalent weight of 200 to 250 g / eq and a poly(propylene oxide)-based polyol (P2) having an average equivalent weight of 475 to 550 g / eq, the ratio P1:P2 being 0.35 to 0.
55.
15. 2. The adhesive of claim 1, wherein the at least one polyol used to make the NCO-terminated prepolymer is a mixture of a poly(propylene oxide)-based diol (P1) having an average equivalent weight of 200-250 g / eq and a poly(propylene oxide)-based diol (P2) having an average equivalent weight of 475-550 g / eq, the ratio P1:P2 being 0.35-0.55.